Positive active material for all-solid-state lithium-ion battery, electrode and all-solid-state lithium-ion battery

By using lithium metal composite oxide particles with specific crystal structure and size characteristics as the positive electrode active substance, the problem of poor lithium ion delivery and reception in all-solid lithium ion batteries is solved, and the effect of improving the first discharge capacity and battery performance is achieved.

CN114982012BActive Publication Date: 2025-02-11TOYOTA JIDOSHA KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080092649.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-01-17
Filing Date
2020-12-23
Publication Date
2025-02-11
Estimated Expiration
2040-12-23

AI Technical Summary

Technical Problem

In all-solid-state lithium-ion secondary batteries, it is difficult to find positive electrode active substances that can smoothly perform lithium ion delivery and increase discharge capacity.

Method used

Particles formed from lithium metal composite oxides have a layered crystal structure of hexagonal crystal form and display a specific crystallographic size ratio and specific surface area range in powder X-ray diffraction measurement of CuKα rays.

Benefits of technology

The first discharge capacity of all solid state lithium-ion batteries is improved, the battery performance is enhanced, and the resistance during charging and discharging is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114982012B_ABST
    Figure CN114982012B_ABST
Patent Text Reader

Abstract

A positive electrode active material for an all-solid-state lithium ion battery, which is an all-solid-state lithium ion battery positive electrode active material formed by particles containing crystals of a lithium metal composite oxide, wherein the particles have a hexagonal layered crystal structure belonging to the space group R-3m, contain at least Li and a transition metal, and, in a powder X-ray diffraction measurement using CuKα rays, a crystallite size L at a diffraction peak within the range of 2θ=18.7±1° 003 The BET specific surface area of ​​the positive electrode active material for the all-solid-state lithium-ion battery is 0.2 m 2 / g or more and 2.0m 2 / g or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a positive electrode active material for an all-solid-state lithium ion battery, an electrode and an all-solid-state lithium ion battery.

[0002] This application claims priority based on Japanese Patent Application No. 2020-006339 filed in Japan on January 17, 2020, the contents of which are incorporated herein by reference. Background Art

[0003] Research on lithium-ion secondary batteries is active for applications such as driving power sources for electric vehicles and household storage batteries. Among them, all-solid-state lithium-ion secondary batteries have advantages such as high energy density, wide operating temperature range, and low degradation compared to existing lithium-ion secondary batteries using electrolytes. Therefore, all-solid-state lithium-ion secondary batteries have attracted much attention as the next generation of energy storage devices.

[0004] In the following description, in order to distinguish from an all-solid lithium ion secondary battery, a “conventional lithium ion secondary battery using an electrolyte solution” may be referred to as a “liquid-based lithium ion secondary battery”.

[0005] Patent Document 1 describes the use of LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 All-solid-state lithium-ion secondary battery with O2 as the positive electrode active material. 1 / 3 Mn 1 / 3 Co 1 / 3 O2 is a material known as a positive electrode active material for liquid lithium ion secondary batteries.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2018-014317 Summary of the invention

[0009] Problems to be solved by the invention

[0010] In the positive electrode of an all-solid-state lithium-ion secondary battery, lithium ions are transferred between the positive electrode active material and the solid electrolyte. In the research of all-solid-state lithium-ion secondary batteries, a positive electrode active material that can smoothly transfer lithium ions and improve battery performance such as discharge capacity has been sought.

[0011] Furthermore, in the research of all-solid-state lithium-ion secondary batteries, the existing research findings of liquid-system lithium-ion secondary batteries may not be utilized. Therefore, research on all-solid-state lithium-ion secondary batteries has become necessary.

[0012] The present invention is carried out in view of such a situation, and the purpose is to provide a positive electrode active material for an all-solid-state lithium ion battery that can improve the initial discharge capacity. In addition, the purpose is also to provide an electrode and an all-solid-state lithium ion battery having such a positive electrode active material for an all-solid-state lithium ion battery.

[0013] The charge and discharge test is carried out under predetermined conditions, and the discharge capacity of the first cycle is defined as the first discharge capacity. If the value of the first discharge capacity is large, the capacity per unit volume and weight is likely to be relatively large.

[0014] Means for solving problems

[0015] In order to solve the above-mentioned problems, the present invention includes the following means.

[0016] [1] A positive electrode active material for an all-solid-state lithium ion battery, the positive electrode active material being formed of particles containing a lithium metal composite oxide crystal, the particles having a hexagonal layered crystal structure belonging to the space group R-3m, containing at least Li and a transition metal, and having a crystallite size L at a diffraction peak within the range of 2θ=18.7±1° in a powder X-ray diffraction measurement using CuKα radiation. 003 for The BET specific surface area of ​​the positive electrode active material for the all-solid-state lithium-ion battery is 0.2 m 2 / g or more and 2.0m 2 / g or less.

[0017] [2] The positive electrode active material for an all-solid-state lithium ion battery according to [1], which is used for an all-solid-state lithium ion battery containing an oxide-based solid electrolyte.

[0018] [3] The positive electrode active material for an all-solid-state lithium ion battery according to [1] or [2], wherein the sum of the mass fractions of K atoms, Fe atoms, Cr atoms, Cu atoms, Ca atoms, Mg atoms and Na atoms relative to the total mass of the positive electrode active material for an all-solid-state lithium ion battery is greater than or equal to 0.03% and less than or equal to 1.0%.

[0019] [4] The positive electrode active material for an all-solid-state lithium ion battery according to any one of [1] to [3], wherein the particles have a L 003 The crystallite size L at the diffraction peak in the range of 2θ = 44.6 ± 1° 104 The ratio of L 003 / L 104 It is 0.70 or more and 3.00 or less.

[0020] [5] The positive electrode active material for an all-solid-state lithium ion battery according to any one of [1] to [4], wherein the particles have a L 003 The crystallite size L at the diffraction peak in the range of 2θ = 64.5 ± 1° 110 The ratio of L 003 / L 110 It is 0.65 or more and 3.00 or less.

[0021] [6] The positive electrode active material for an all-solid-state lithium ion battery according to any one of [1] to [5], wherein the transition metal is at least one element selected from the group consisting of Ni, Co, Mn, Ti, V and W.

[0022] [7] The positive electrode active material for an all-solid-state lithium-ion battery according to [6], wherein the lithium metal composite oxide is represented by the composition formula (A) shown below.

[0023] Li[Li x (Ni (1-y-z-w) Co y Mn z M w ) 1-x ]O2 Composition formula (A)

[0024] (Wherein, M is one or more elements selected from the group consisting of Ti, Al, W, B, Mo, Nb, Zn, Sn, Zr, Ga, and V, and satisfies -0.10≤x≤0.30, 0≤y≤0.40, 0≤z≤0.40, and 0≤w≤0.10.)

[0025] [8] The positive electrode active material for an all-solid-state lithium-ion battery according to [7], wherein the composition formula (A) satisfies y>0 and z+w>0.

[0026] [9] The positive electrode active material for an all-solid-state lithium ion battery according to [7] or [8], wherein the composition formula (A) satisfies 1-yzw≥0.50 and y≤0.30.

[0027]

[10] A positive electrode active material for an all-solid-state lithium-ion battery according to any one of [1] to [9], wherein the particles are composed of primary particles, secondary particles which are agglomerates of the primary particles, and single particles which exist independently of the primary particles and the secondary particles, and the content of the single particles in the particles is greater than 20%.

[0028]

[11] An electrode comprising the positive electrode active material for an all-solid-state lithium ion battery according to any one of [1] to

[10] .

[0029]

[12] The electrode according to

[11] , further comprising a solid electrolyte.

[0030]

[13] An all-solid-state lithium-ion battery comprising a positive electrode, a negative electrode and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, the solid electrolyte layer comprising a first solid electrolyte, the positive electrode comprising a positive electrode active material layer in contact with the solid electrolyte layer and a current collector stacked with the positive electrode active material layer, the positive electrode active material layer comprising the positive electrode active material for an all-solid-state lithium-ion battery described in any one of [1] to

[10] .

[0031]

[14] The all-solid-state lithium ion battery according to

[13] , wherein the positive electrode active material layer comprises the positive electrode active material for the all-solid-state lithium ion battery and a second solid electrolyte.

[0032]

[15] The all-solid-state lithium-ion battery according to

[14] , wherein the first solid electrolyte and the second solid electrolyte are the same substance.

[0033]

[16] The all-solid-state lithium-ion battery according to any one of

[13] to

[15] , wherein the first solid electrolyte has an amorphous structure.

[0034]

[17] The all-solid-state lithium-ion battery according to any one of

[13] to

[16] , wherein the first solid electrolyte is an oxide-based solid electrolyte.

[0035] Effects of the Invention

[0036] According to the present invention, a positive electrode active material for an all-solid-state lithium ion battery capable of improving the initial discharge capacity can be provided. In addition, an electrode and an all-solid-state lithium ion battery having such a positive electrode active material for an all-solid-state lithium ion battery can also be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a schematic diagram showing a stacked body included in the all-solid-state lithium-ion battery according to the embodiment.

[0038] Figure 2 It is a schematic diagram showing the overall structure of an all-solid-state lithium-ion battery according to an embodiment. DETAILED DESCRIPTION

[0039] <Positive electrode active material for all-solid-state lithium-ion batteries>

[0040] When the surface of the particulate lithium metal composite oxide has a coating layer formed of a metal composite oxide described later, the particles having the coating layer correspond to “particles containing crystals of a lithium metal composite oxide” in one embodiment of the present invention.

[0041] When the surface of the particulate lithium metal composite oxide does not have a coating layer formed of the metal composite oxide, the lithium metal composite oxide corresponds to the “particles containing crystals of the lithium metal composite oxide” in one embodiment of the present invention.

[0042] The positive electrode active material for all-solid-state lithium ion batteries is a particle containing crystals of a lithium metal composite oxide. The positive electrode active material for all-solid-state lithium ion batteries of the present embodiment is a positive electrode active material suitable for all-solid-state lithium ion batteries containing an oxide-based solid electrolyte.

[0043] Hereinafter, the positive electrode active material for the all-solid-state lithium ion battery according to the present embodiment may be simply referred to as “positive electrode active material”.

[0044] The positive electrode active material satisfies the following requirements.

[0045] (Requirement 1) The particles contained in the positive electrode active material have a hexagonal layered crystal structure belonging to the space group R-3m and contain at least Li and a transition metal. In addition, in this specification, the transition metal refers to a transition metal element.

[0046] (Requirement 2) The particles contained in the positive electrode active material have a crystallite size L at a diffraction peak within the range of 2θ=18.7±1° in powder X-ray diffraction measurement using CuKα radiation. 003 for the following.

[0047] (Requirement 3) The BET specific surface area of ​​the positive electrode active material is 0.2 m 2 / g or more and 2.0m 2 / g or less.

[0048] The following will explain them one by one.

[0049] (Requirement 1)

[0050] The particles have a hexagonal layered crystal structure belonging to space group R-3m and contain at least Li and a transition metal. The transition metal may be at least one selected from the group consisting of Ni, Co, Mn, Ti, V and W.

[0051] In this specification, Ni does not refer to nickel metal but refers to nickel atoms, and metal species such as Co and Li also refer to metal atoms such as cobalt atoms and lithium atoms, respectively.

[0052] The particles contain at least one element selected from the group consisting of Ni, Co and Mn as a transition metal, and the resulting positive electrode active material forms a stable crystal structure in which Li ions can be deintercalated or intercalated. Therefore, when the positive electrode active material is used for the positive electrode of an all-solid-state lithium-ion battery, a high charge capacity and a high first discharge capacity can be obtained.

[0053] In addition, when the particles include at least one selected from the group consisting of Ti, Fe, V and W, the crystal structure of the obtained positive electrode active material becomes strong. Therefore, the positive electrode active material has high thermal stability. In addition, such a positive electrode active material can improve the cycle characteristics of the all-solid-state lithium ion battery.

[0054] The lithium metal composite oxide contained in the positive electrode active material preferably contains at least Li, Ni and one or more elements selected from the group consisting of Co, Mn, Ti, Al, W, B, Mo, Nb, Zn, Sn, Zr, Ga and V, and is preferably represented by the following composition formula (A).

[0055] Li[Li x (Ni (1-y-z-w) Co y Mn z M w ) 1-x ]O2 (A)

[0056] (Wherein, M is one or more elements selected from the group consisting of Ti, Al, W, B, Mo, Nb, Zn, Sn, Zr, Ga, and V, and satisfies -0.10≤x≤0.30, 0≤y≤0.40, 0≤z≤0.40, and 0≤w≤0.10.)

[0057] (About x)

[0058] From the perspective of obtaining an all-solid-state lithium-ion battery with good cycle characteristics, x is preferably greater than 0, more preferably greater than 0.01, and further preferably greater than 0.02. In addition, from the perspective of obtaining an all-solid-state lithium-ion battery with a higher first Coulomb effect, x is preferably less than 0.25, and more preferably less than 0.10.

[0059] In this specification, “good cycle characteristics” refers to characteristics in which the battery capacity decreases less due to repeated charge and discharge, and means that the capacity ratio to the initial capacity is less likely to decrease when re-measured.

[0060] In addition, the "first Coulomb effect" in this specification is a value calculated by "(first discharge capacity) / (first charge capacity)×100(%)". For all-solid-state lithium-ion batteries with a high first Coulomb effect, the irreversible capacity during the first charge and discharge is small, and the capacity per unit volume and weight is relatively easy to increase.

[0061] The upper limit and lower limit of x may be arbitrarily combined. x may be -0.10 to 0.25, or -0.10 to 0.10.

[0062] x may be greater than 0 and less than 0.30, greater than 0 and less than 0.25, or greater than 0 and less than 0.10.

[0063] x may be 0.01 to 0.30, 0.01 to 0.25, or 0.01 to 0.10.

[0064] x may be 0.02 to 0.3, 0.02 to 0.25, or 0.02 to 0.10.

[0065] x preferably satisfies 0<x≤0.30.

[0066] (About y)

[0067] From the viewpoint of obtaining an all-solid-state lithium-ion battery with a low internal resistance of the battery, y is preferably greater than 0, more preferably greater than 0.005, further preferably greater than 0.01, and particularly preferably greater than 0.05. In addition, from the viewpoint of obtaining an all-solid-state lithium-ion battery with high thermal stability, y is more preferably less than 0.35, further preferably less than 0.33, and further preferably less than 0.30.

[0068] The upper limit and lower limit of y may be arbitrarily combined. y may be 0 to 0.35, 0 to 0.33, or 0 to 0.30.

[0069] y may be greater than 0 and less than 0.40, greater than 0 and less than 0.35, greater than 0 and less than 0.33, or greater than 0 and less than 0.30.

[0070] y may be 0.005 or more and 0.40 or less, 0.005 or more and 0.35 or less, 0.005 or more and 0.33 or less, or 0.005 or more and 0.30 or less.

[0071] y may be 0.01 to 0.40, 0.01 to 0.35, 0.01 to 0.33, or 0.01 to 0.30.

[0072] y may be 0.05 to 0.40, 0.05 to 0.35, 0.05 to 0.33, or 0.05 to 0.30.

[0073] y preferably satisfies 0<y≤0.40, and more preferably satisfies 0<y≤0.30.

[0074] In the composition formula (A), 0<x≤0.10 and 0<y≤0.40 are more preferably satisfied, and 0<x≤0.10 and 0<y≤0.30 are further preferably satisfied.

[0075] (About z)

[0076] From the viewpoint of obtaining an all-solid-state lithium-ion battery with high cycle characteristics, z is preferably greater than 0, z is more preferably greater than 0.01, further preferably greater than 0.02, and particularly preferably greater than 0.10. In addition, from the viewpoint of obtaining an all-solid-state lithium-ion battery with high storage properties at high temperatures (e.g., 60°C), z is preferably less than 0.39, more preferably less than 0.38, and further preferably less than 0.35.

[0077] The upper limit and lower limit of z may be arbitrarily combined. z may be 0 or more and 0.39 or less, 0 or more and 0.38 or less, 0 or more and 0.35 or less, or more than 0 and 0.39 or less.

[0078] z may be 0.01 to 0.40, 0.01 to 0.39, 0.01 to 0.38, or 0.01 to 0.35.

[0079] z may be 0.02 or more and 0.40 or less, 0.02 or more and 0.39 or less, 0.02 or more and 0.38 or less, or 0.02 or more and 0.35 or less.

[0080] z may be 0.10 to 0.40, 0.10 to 0.39, 0.10 to 0.38, or 0.10 to 0.35.

[0081] z preferably satisfies 0.02≤z≤0.35.

[0082] In composition formula (A), y>0 and z+w>0 are preferably satisfied.

[0083] (About w)

[0084] From the viewpoint of obtaining an all-solid-state lithium-ion battery with a low internal resistance of the battery, w is preferably greater than 0, more preferably greater than 0.0005, and further preferably greater than 0.001. In addition, from the viewpoint of obtaining an all-solid-state lithium-ion battery with a large first discharge capacity at a high current rate, w is preferably less than 0.09, more preferably less than 0.08, and further preferably less than 0.07.

[0085] The upper limit and lower limit of w may be arbitrarily combined. w may be 0 to 0.09, 0 to 0.08, or 0 to 0.07.

[0086] w may be greater than 0 and less than 0.10, greater than 0 and less than 0.09, greater than 0 and less than 0.08, or greater than 0 and less than 0.07.

[0087] w may be 0.0005 or more and 0.10 or less, 0.0005 or more and 0.09 or less, 0.0005 or more and 0.08 or less, or 0.0005 or more and 0.07 or less.

[0088] w may be 0.001 to 0.10, 0.001 to 0.09, 0.001 to 0.08, or 0.001 to 0.07.

[0089] w preferably satisfies 0≤w≤0.07.

[0090] (About y+z+w)

[0091] From the viewpoint of obtaining an all-solid-state lithium ion battery with a large battery capacity, y+z+w in the composition formula (A) is preferably 0.50 or less, more preferably 0.48 or less, and even more preferably 0.46 or less.

[0092] y+z+w in composition formula (A) exceeds 0, is preferably 0.001 or more, and more preferably 0.002 or more.

[0093] The upper limit and lower limit of y+z+w may be arbitrarily combined. y+z+w is preferably greater than 0 and less than 0.50, more preferably greater than 0.001 and less than 0.48, and still more preferably greater than 0.002 and less than 0.46.

[0094] The composition formula (A) preferably satisfies 1-yzw≥0.50 and y≤0.30. That is, the lithium metal composite oxide contained in the positive electrode active material preferably has a Ni content molar ratio of 0.50 or more and a Co content molar ratio of 0.30 or less in the composition formula (A).

[0095] (About M)

[0096] M represents one or more elements selected from the group consisting of Ti, Al, W, B, Mo, Nb, Zn, Sn, Zr, Ga, La, and V.

[0097] In addition, from the viewpoint of obtaining an all-solid-state lithium-ion battery with high cycle characteristics, M in the composition formula (A) is preferably an element selected from the group consisting of Ti, Al, Nb, W, B and Zr, and more preferably an element selected from the group consisting of Al, Nb and Zr. In addition, from the viewpoint of obtaining an all-solid-state lithium-ion battery with high thermal stability, it is preferably an element selected from the group consisting of Ti, Al, Nb, W, B and Zr.

[0098] An example of a preferred combination of the above-mentioned x, y, z, and w includes: an example in which x is greater than 0.02 and less than 0.30, y is greater than 0.05 and less than 0.30, z is greater than 0.02 and less than 0.35, and w is greater than 0 and less than 0.07; an example in which x exceeds 0 and is less than 0.10, y exceeds 0 and is less than 0.30, z is greater than 0 and less than 0.35, w is greater than 0 and less than 0.07, and z+w exceeds 0.

[0099] <Composition Analysis>

[0100] The composition analysis of the particles or lithium metal composite oxide in the positive electrode active material can be confirmed by dissolving the obtained particles of the positive electrode active material in hydrochloric acid and then performing composition analysis using an inductively coupled plasma emission spectrometer.

[0101] It should be noted that the composition of the lithium metal composite oxide is consistent with the composition obtained by making the above-mentioned composition analysis results of the positive electrode active material correspond to the composition formula (A). That is, the values ​​of x, y, z and w obtained by making the analysis results of the positive electrode active material correspond to the composition formula (A) can be regarded as the values ​​of x, y, z and w of the lithium metal composite oxide.

[0102] As the inductively coupled plasma emission analysis apparatus, for example, SPS3000 manufactured by SII NanoTechnology Co., Ltd. can be used.

[0103] It should be noted that the all-solid-state lithium-ion battery is charged by applying a negative potential to the positive electrode and a positive potential to the negative electrode by an external power source.

[0104] In addition, the discharge of the all-solid-state lithium-ion battery is performed by connecting a discharge circuit to the positive and negative electrodes of the charged all-solid-state lithium-ion battery and energizing the discharge circuit. The discharge circuit includes electronic equipment, electrical equipment, and electric vehicles driven by the power of the all-solid-state lithium-ion battery.

[0105] (Crystal Structure of Particles in Positive Electrode Active Material)

[0106] The particles in the positive electrode active material have a hexagonal layered crystal structure belonging to the space group R-3m.

[0107] The crystal structure of the particles in the positive electrode active material can be confirmed by powder X-ray diffraction or electron beam diffraction.

[0108] The hexagonal crystal structure belongs to a group consisting of P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65, P Any space group in the group consisting of P62, P64, P63, P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mm, P6 / mcc, P63 / mcm and P63 / mmc.

[0109] <Method for Confirming the Crystal Structure>

[0110] The above-mentioned crystal structure can be confirmed by observation using a powder X-ray diffraction measuring apparatus.

[0111] The powder X-ray diffraction measurement can be performed using an X-ray diffractometer. As the X-ray diffractometer, for example, Ultima IV manufactured by Rigaku Corporation can be used.

[0112] (Requirement 2)

[0113] The crystallite size L of the above particles at the diffraction peak within the range of 2θ=18.7±1° in powder X-ray diffraction measurement using CuKα radiation is 003 for The following are preferably The following are more preferably The following are particularly preferred the following.

[0114] The above L 003 It can also be above, above, above.

[0115] The above L 003 The upper and lower limits can be combined arbitrarily.

[0116] As a combination example, the above L 003 for Above and the following, Above and the following, Above and the following.

[0117] <The above L 003 Determination method>

[0118] The above L 003 It can be measured by powder X-ray diffraction measurement.

[0119] The powder X-ray diffraction measurement may be performed using an X-ray diffractometer. As the X-ray diffractometer, for example, Ultima IV manufactured by Rigaku Corporation can be used.

[0120] Specifically, first, a powder of the positive electrode active material including the above particles is filled in a dedicated substrate, and a Cu-Kα ray source is used to perform measurement to obtain a powder X-ray diffraction pattern. An example of the measurement conditions is described below.

[0121] (Measurement conditions)

[0122] Diffraction angle 2θ = 10°~90°

[0123] Sampling amplitude 0.02°

[0124] Scanning speed 4° / min

[0125] The crystallite size L at the diffraction peak within the range of 2θ = 18.7 ± 1° was calculated from the obtained powder X-ray diffraction pattern using the comprehensive powder X-ray analysis software JADE using the tools on the software. 003 .

[0126] (Requirement 3)

[0127] The BET specific surface area of ​​the positive electrode active material is 0.2 m 2 / g or more and 2.0m 2 / g or less.

[0128] The lower limit of the BET specific surface area is preferably 0.21 m2 0.21 m² / g or more, more preferably 0.22 m² / g or more 2 0.22 m² / g or more, particularly preferably 0.23 m² / g or more 2 0.23 m² / g or more

[0129] The upper limit of the BET specific surface area is preferably 1.99 m² / g or less, more preferably 1.98 m² / g or less 2 0.21 m² / g or more, more preferably 0.22 m² / g or more 2 0.22 m² / g or more, particularly preferably 0.23 m² / g or more 2 0.23 m² / g or more

[0130] The above upper and lower limits of the BET specific surface area can be arbitrarily combined

[0131] As a combination example, there can be mentioned a BET specific surface area of 0.21 m² / g or more and 1.99 m² / g or less, 0.22 m² / g or more and 1.98 m² / g or less, 0.23 m² / g or more and 1.97 m² / g or less 2 0.21 m² / g or more and 1.99 m² / g or less 2 0.22 m² / g or more 2 0.22 m² / g or more and 1.98 m² / g or less 2 0.23 m² / g or more 2 0.23 m² / g or more and 1.97 m² / g or less 2 0.23 m² / g or more and 1.97 m² / g or less

[0132] <Method for measuring BET specific surface area>

[0133] The BET specific surface area can be measured by the following method

[0134] After drying 1 g of the positive electrode active material in a nitrogen atmosphere at 105 °C for 30 minutes, it is measured using a BET specific surface area measuring device

[0135] As the BET specific surface area measuring device, for example, Macsorb (registered trademark) manufactured by MOUNTECH Co., Ltd. can be used

[0136] The positive electrode active material preferably further satisfies the following requirements 4 to 6

[0137] (Requirement 4)

[0138] Regarding the positive electrode active material, the sum of the mass fractions of K atoms, Fe atoms, Cr atoms, Cu atoms, Ca atoms, Mg atoms, and Na atoms with respect to the total mass of the positive electrode active material is 0.03% or more and 1.0% or less. Hereinafter, K atoms, Fe atoms, Cr atoms, Cu atoms, Ca atoms, Mg atoms, and Na atoms may sometimes be referred to as "impurity atoms".

[0139] <Method for measuring the amount of impurity atoms in the positive electrode active material>

[0140] The sum of the mass fractions of the impurity atoms is calculated as follows

[0141] First, using an inductively coupled plasma atomic emission spectrometer (ICP-AES), the mass fractions of Li atoms, Ni atoms, Co atoms, Mn atoms, B atoms, Zr atoms, Al atoms, and impurity atoms contained in the positive electrode active material are analyzed and calculated.

[0142] Next, the sum of the mass fractions of impurity atoms is calculated.

[0143] As the inductively coupled plasma emission spectrometry analyzer, for example, SPS3000 manufactured by SII NanoTechnology Co., Ltd. can be used.

[0144] The sum of the mass fractions of impurity atoms is preferably 0.04% or more, more preferably 0.06% or more, and particularly preferably 0.05% or more.

[0145] The sum of the mass fractions of impurity atoms is preferably 0.9% or less, more preferably 0.85% or less, and particularly preferably 0.8% or less.

[0146] The above upper limit values ​​and lower limit values ​​may be arbitrarily combined.

[0147] Examples of the combination include a case where the sum of the mass fractions of impurity atoms is 0.11% to 0.9%, 0.12% to 0.85%, and 0.13% to 0.8%.

[0148] The fact that the sum of the mass fractions of impurity atoms in the positive electrode active material satisfies the above lower limit or more means that excessive crystal growth is suppressed.

[0149] A positive electrode active material having a sum of mass fractions of impurity atoms satisfying the above upper limit or less has a small amount of impurity atoms that may serve as resistance during charge and discharge, and can increase the initial discharge capacity.

[0150] (Requirement 5)

[0151] In the powder X-ray diffraction measurement of the above particles using CuKα radiation, the above L 003 The crystallite size L at the diffraction peak in the range of 2θ = 44.6 ± 1° 104 The ratio (L 003 / L 104 ) is preferably greater than or equal to 0.70 and less than or equal to 3.00.

[0152] Ratio (L 003 / L 104 ) is preferably 0.70 or more, more preferably 0.80 or more, particularly preferably 0.90 or more.

[0153] Ratio (L 003 / L 104) is preferably 3.00 or less, more preferably 2.50 or less, particularly preferably 2.00 or less.

[0154] Ratio (L 003 / L 104 ) can be combined arbitrarily.

[0155] As a combination example, the ratio (L 003 / L 104 ) is 0.08 or more and 2.50 or less, and 0.09 or more and 2.00 or less.

[0156] If the ratio (L 003 / L 104 ) is within the above range, the proportion of crystal faces in the microcrystals of the positive electrode active material that can contribute to the insertion and extraction of Li becomes higher, thereby reducing the resistance during charging and discharging and increasing the initial discharge capacity.

[0157] <(L 003 / L 104 ) calculation method>

[0158] Ratio (L 003 / L 104 ) is measured by powder X-ray diffraction measurement. 003 and the above L 104 Then calculate.

[0159] For the above L 104 , except for the diffraction peak within the range of 2θ=44.6±1°, the above L 003 The same method was used to measure and the ratio (L 003 / L 104 ).

[0160] (Requirement 6)

[0161] In the powder X-ray diffraction measurement of the above particles using CuKα radiation, the above L 003 The crystallite size L at the diffraction peak in the range of 2θ = 64.5 ± 1° 110 The ratio (L 003 / L 110 ) is preferably greater than or equal to 0.65 and less than or equal to 3.00.

[0162] Ratio (L 003 / L 110 ) is preferably 0.65 or more, more preferably 0.70 or more, particularly preferably 0.80 or more.

[0163] Ratio (L 003 / L 110) is preferably 3.00 or less, more preferably 2.50 or less, particularly preferably 2.00 or less.

[0164] Ratio (L 003 / L 110 ) can be combined arbitrarily.

[0165] As a combination example, the ratio (L 003 / L 110 ) is 0.70 to 2.50, and 0.80 to 2.00.

[0166] If the ratio (L 003 / L 110 ) is within the above range, the stress of the expansion and contraction of the lattice of the positive electrode active material during the charging and discharging process is dispersed in an equal direction. Therefore, the cracking of the particles of the positive electrode active material can be prevented during the first charge, thereby increasing the first discharge capacity.

[0167] <(L 003 / L 110 ) calculation method>

[0168] Ratio (L 003 / L 110 ) is measured by powder X-ray diffraction measurement. 003 and the above L 110 Then calculate.

[0169] For the above L 110 , except for the diffraction peak within the range of 2θ=64.5±1°, the above L 003 The same method was used to measure and the ratio (L 003 / L 110 ).

[0170] The inventors' research has revealed that even if the positive electrode active material shows good battery performance such as the first discharge capacity when used in the positive electrode of an existing liquid lithium-ion secondary battery, some of them have insufficient performance when used in the positive electrode of an all-solid-state lithium-ion battery. Based on this insight into all-solid-state lithium-ion secondary batteries, the inventors conducted research and found that the positive electrode active material that meets the above-mentioned requirements 1 to 3 can improve the first discharge capacity even when used in the positive electrode of an all-solid-state lithium-ion battery.

[0171] First, the positive electrode active material satisfies requirement 1 and can well perform intercalation and deintercalation of lithium ions.

[0172] Furthermore, the positive electrode active material satisfies requirements 2 to 3. In the positive electrode of the all-solid-state lithium ion secondary battery, the positive electrode active material transfers lithium ions between the positive electrode active material and the solid electrolyte.

[0173] The positive electrode active material expands during charging. If the expansion is large, the particles will crack and new surfaces will be generated. The new surfaces generated by particle cracking can become resistors when lithium ions move. In addition, the new surfaces are not easy to become interfaces with solid electrolytes. Therefore, it is preferred that particles are not easy to crack when the crystal expands.

[0174] Regarding the positive electrode active material that satisfies requirement 2, the crystallite size of the particles in the positive electrode active material is small, and the amplitude of crystal expansion during the first charge becomes small. In this case, the particles become less likely to crack when the crystal expands. If such a positive electrode active material is used, the generation of new surfaces that can become resistors is less likely to occur, so the first discharge capacity can be increased.

[0175] If a positive electrode active material that satisfies the lower limit of requirement 3 is used, the contact area between the positive electrode active materials or between the positive electrode active material and the solid electrolyte can be fully ensured. In addition, if the upper limit of requirement 3 is met, the surface roughness of the particles decreases, and the contact area between the positive electrode active materials or between the positive electrode active material and the solid electrolyte can be increased.

[0176] For the reasons described above, when a positive electrode active material satisfying requirements 1 to 3 is used in a positive electrode of an all-solid-state lithium ion battery, it is possible to increase the initial discharge capacity.

[0177] The battery performance of the all-solid-state lithium-ion battery can be evaluated by the initial discharge capacity obtained by the following method.

[0178] <Manufacturing of all-solid-state lithium-ion secondary batteries>

[0179] (Manufacturing of positive electrode active material sheet)

[0180] The positive electrode active material and Li3BO3 were mixed in a ratio of positive electrode active material: Li3BO3 = 80:20 (molar ratio) to obtain a mixed powder. A resin binder (ethyl cellulose), a plasticizer (dioctyl phthalate) and a solvent (acetone) were added to the obtained mixed powder in a ratio of mixed powder: resin binder: plasticizer: solvent = 100:10:10:100 (mass ratio), and mixed using a planetary stirring / degassing device.

[0181] The obtained slurry was degassed using a planetary stirring / degassing device to obtain a positive electrode mixture slurry.

[0182] The obtained positive electrode mixture slurry was applied onto a PET film using a doctor blade, and the applied film was dried to form a positive electrode film with a thickness of 50 μm.

[0183] The positive electrode film was peeled from the PET film and punched into a circular shape with a diameter of 14.5 mm. The positive electrode film was then uniaxially pressed at 20 MPa for 1 minute in the thickness direction of the positive electrode film to obtain a positive electrode active material sheet with a thickness of 40 μm.

[0184] (Manufacturing of all-solid-state lithium-ion batteries)

[0185] The positive electrode active material sheet and Li 6.75 Ln3Z 1.75 Nb 0.25 O 12 Solid electrolyte pellets (for example, manufactured by Toyoshima Seisakusho Co., Ltd.) are stacked and uniaxially pressed in parallel with the stacking direction to obtain a stacked body.

[0186] A positive electrode current collector (gold foil, 500 μm thick) was further stacked on the positive electrode active material sheet of the obtained laminate, and the organic components were burned out by heating at 300°C for 1 hour under a pressure of 100 gf. The temperature was further increased to 800°C at 5°C / min, and then sintered at 800°C for 1 hour to obtain a laminate of a solid electrolyte layer and a positive electrode.

[0187] Next, the following operations were performed in a glove box with an argon atmosphere.

[0188] A negative electrode (Li foil, 300 μm thick), a negative electrode collector (stainless steel plate, 50 μm thick), and a corrugated washer (made of stainless steel) were further stacked on the solid electrolyte layer in the stack of the solid electrolyte layer and the positive electrode.

[0189] For the stacked body formed by overlapping from the positive electrode to the corrugated gasket, the positive electrode is placed on the lower cover of the component for coin-type battery R2032 (produced by Hohsen Co., Ltd.), overlapped with the corrugated gasket and covered with the upper cover, and riveted with a riveting machine to produce an all-solid-state lithium-ion battery.

[0190] <Determination of initial discharge capacity>

[0191] Using the all-solid-state lithium-ion battery produced by the above method, an initial charge and discharge test was carried out under the following conditions, and the initial discharge capacity was calculated.

[0192] <First charge and discharge test conditions>

[0193] Test temperature: 60℃

[0194] Maximum charging voltage 4.3V, charging current 0.01CA, cut-off current 0.002CA, constant current and constant voltage charging

[0195] Minimum discharge voltage 2.5V, discharge current 0.01CA, constant current discharge

[0196] (Other components 1)

[0197] In the positive electrode active material of the present embodiment, particles constituting the positive electrode active material are preferably formed of primary particles, secondary particles that are aggregates of the primary particles, and single particles that exist independently of the primary particles and the secondary particles.

[0198] <Method for Confirming Particle Shape>

[0199] In the present invention, the "primary particles" refer to particles having no crystal grain boundaries in appearance when observed with a scanning electron microscope at a visual field of 20,000 times and having a particle size of less than 0.5 μm.

[0200] In the present invention, "secondary particles" refer to particles formed by aggregation of primary particles. When the secondary particles are observed with a scanning electron microscope at a field of view of 20,000 times, they have crystal boundaries in appearance.

[0201] In the present invention, a “single particle” refers to a particle that exists independently of secondary particles and has no grain boundaries in appearance when observed with a scanning electron microscope at a field of view of 20,000 times and has a particle diameter of 0.5 μm or more.

[0202] That is, the positive electrode active material of the present embodiment is composed of particles that appear to have no grain boundaries and particles that appear to have grain boundaries when observed with a scanning electron microscope at a field of view of 20,000 times.

[0203] Particles with no apparent grain boundaries are composed of "primary particles" with a small particle size and "single particles" with a large particle size, based on a particle size of 0.5 μm.

[0204] The particles having crystal grain boundaries in appearance are "secondary particles" which are aggregated particles of the above-mentioned "primary particles".

[0205] In the positive electrode active material of the present embodiment, the content of single particles in the whole particle is preferably 20% or more. When the positive electrode active material in which the content of single particles in the whole particle is 20% or more in terms of the number of particles is used in an all-solid-state battery, it is easy to ensure the contact interface with the solid electrolyte in the positive electrode layer, and the conduction of lithium ions passing through the interface is smoothly performed.

[0206] In addition, since there are no grain boundaries in the single particles of the positive electrode active material with a single particle content of more than 20% in the whole particle, even if it is used as the positive electrode of an all-solid-state lithium-ion battery for repeated charging and discharging, the particles are not easy to crack and the conductive path is easy to maintain.

[0207] <Calculation method of single particle content>

[0208] The content rate of single particles in the positive electrode active material was calculated by the following method.

[0209] The powder of the positive electrode active material is observed using a scanning electron microscope at 20,000 times, and the number of single particles and secondary particles are counted in the observed field of view. The number of single particles is set to N1, the number of secondary particles is set to N2, and the number ratio of single particles is calculated by N1 / (N1+N2)[%]. It should be noted that when the number of observable particles is less than 50, multiple continuous fields of view are obtained until 50 particles can be confirmed for observation.

[0210] The average particle size of a single particle is preferably 0.5 μm or more, and more preferably 1.0 μm or more. In addition, the average particle size of a single particle is preferably 10 μm or less, and more preferably 5 μm or less.

[0211] The upper limit value and the lower limit value of the average particle size of a single particle may be arbitrarily combined.

[0212] The combination of the upper limit value and the lower limit value of the average particle size of a single particle may be 0.5 μm or more and 10 μm or less, and 1.0 μm or more and 5 μm or less.

[0213] The average particle size of the secondary particles is preferably 3.0 μm or more, and more preferably 5.0 μm or more. In addition, the average particle size of the secondary particles is preferably 15 μm or less, and more preferably 10 μm or less.

[0214] The upper limit value and the lower limit value of the average particle size of the secondary particles may be arbitrarily combined.

[0215] Examples of the combination of the upper limit and the lower limit of the average particle size of the secondary particles include 3.0 μm or more and 15 μm or less and 5.0 μm or more and 10 μm or less.

[0216] The average particle diameters of single particles and secondary particles can be measured by the following method.

[0217] First, the positive electrode active material was placed on a conductive sheet attached to a sample stage, and then irradiated with electron beams at an accelerating voltage of 20 kV using a scanning electron microscope (JSM-5510 manufactured by JEOL Ltd.) and observed at a field of view of 20,000 times.

[0218] Next, 50 or more and 98 or less single particles or secondary particles are extracted from the obtained electron microscope image (SEM photograph) by the following method.

[0219] (Single particle extraction method)

[0220] When measuring the average particle size of single particles, all single particles contained in one field of view are set as measurement objects in a 20,000-fold magnification field of view. When the number of single particles contained in one field of view is less than 50, single particles in multiple fields of view are set as measurement objects until the number of measurements reaches 50 or more.

[0221] (Method for extracting secondary particles)

[0222] When measuring the average particle size of secondary particles, all secondary particles contained in one field of view are set as the measurement object in a 20,000-fold magnification field of view. When the number of secondary particles contained in one field of view is less than 50, the secondary particles in multiple fields of view are set as the measurement object until the number of measured particles reaches 50 or more.

[0223] For the image of the extracted single particle or secondary particle, the distance between parallel lines when sandwiched by parallel lines drawn from a fixed direction (orientation diameter) is measured as the particle size of the single particle or secondary particle.

[0224] The arithmetic mean of the particle sizes of the obtained single particles or secondary particles is the average particle size of the single particles contained in the positive electrode active material or the average particle size of the secondary particles contained in the positive electrode active material.

[0225] (Other components 2)

[0226] The positive electrode active material preferably has a coating layer formed of a metal composite oxide on the surface of the lithium metal composite oxide.

[0227] As the metal composite oxide constituting the coating layer, an oxide having lithium ion conductivity is preferably used.

[0228] It is known that even if the metal composite oxide constituting the coating layer does not have lithium ion conductivity, as long as the coating layer is a very thin film (for example, 0.1 nm or more and 1.0 nm or less), the battery performance is improved compared to the positive electrode active material without the coating layer. In this case, it is presumed that lithium ion conductivity is manifested in the coating layer. However, the method of manufacturing by controlling the uniform coating layer on the surface to a thickness of less than 1.0 nm is limited to a method of insufficient mass production.

[0229] In contrast, if the metal composite oxide constituting the coating layer has lithium ion conductivity, the coating layer can preferably conduct lithium ions even if the coating layer has a thickness of about 5 nm to 20 nm, thereby improving battery performance, which is preferred.

[0230] It should be noted that the thickness of the coating layer can be measured by taking the positive electrode active material having a maximum diameter of 50% cumulative volume particle size D50 (μm) ± 5% obtained by laser diffraction particle size distribution measurement as an object. The arithmetic mean of the values ​​obtained by measuring 10 particles is set as the thickness of the coating layer.

[0231] For the particles of the positive electrode active material as the measurement object, the average thickness of the coating layer is obtained by using the analysis results of the scanning transmission electron microscope (STEM)-energy dispersive X-ray spectroscopy (EDX). The line profile of the element unique to the coating layer is made, and based on the obtained line profile, the range in which the above-mentioned unique element is detected is set as the existence range of the coating layer, so that the thickness of the coating layer can be obtained.

[0232] Examples of such metal composite oxides include metal composite oxides of Li and at least one element selected from the group consisting of Nb, Ge, Si, P, Al, W, Ta, Ti, S, Zr, Zn, V, and B.

[0233] If the positive electrode active material has a coating layer, a high resistance layer is not easily formed at the interface between the positive electrode active material and the solid electrolyte, and a high output of the all-solid-state battery can be achieved. Such an effect is particularly easy to obtain in a sulfide-based all-solid-state battery using a sulfide-based solid electrolyte as the solid electrolyte.

[0234] <Method 1 for producing positive electrode active material>

[0235] When producing the lithium metal composite oxide, first, a metal composite compound containing a metal element other than Li among the metal elements constituting the lithium metal composite oxide is prepared, and then the metal composite compound is preferably calcined with a lithium compound and an inactive flux.

[0236] Specifically, a “metal composite compound” is a compound containing Ni as an essential metal element and any one or more of Co, Mn, Fe, Cu, Ti, Mg, Al, W, B, Mo, Nb, Zn, Sn, Zr, Ga, La and V.

[0237] As the metal composite compound, a metal composite hydroxide or a metal composite oxide is preferable.

[0238] Hereinafter, an example of a method for producing a positive electrode active material will be described separately by a process for producing a metal composite compound and a process for producing a lithium metal composite oxide.

[0239] (Metal Composite Compound Manufacturing Process)

[0240] The metal composite compound can be manufactured by a commonly known coprecipitation method. As the coprecipitation method, a commonly known intermittent coprecipitation method or a continuous coprecipitation method can be used. Below, the manufacturing method of the metal composite compound is described in detail by taking a metal composite hydroxide containing Ni, Co and Mn as metal elements as an example.

[0241] First, a nickel salt solution, a cobalt salt solution, a manganese salt solution and a complexing agent are reacted by a coprecipitation method, particularly a continuous coprecipitation method described in Japanese Patent Application Laid-Open No. 2002-201028, to produce a nickel-containing (1-y-z) Co y Mn z A metal composite hydroxide represented by (OH)2 (wherein y+z<1).

[0242] The nickel salt used as the solute of the nickel salt solution is not particularly limited, and for example, any one or two or more of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate can be used.

[0243] As the cobalt salt serving as the solute of the cobalt salt solution, for example, one or more of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate may be used.

[0244] As the manganese salt serving as the solute of the manganese salt solution, for example, any one or two or more of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate may be used.

[0245] The above metal salts are used with the above Ni (1-y-z) Co y Mn z That is, the molar ratio of each metal salt is Ni in the solute of the nickel salt solution, Co in the solute of the cobalt salt solution, and Mn in the solute of the manganese salt solution. (1-y-z) Co y Mn z The composition ratio of (OH)2 is used in the amount of (1-yz):y:z.

[0246] In addition, the solvent of the nickel salt solution, the cobalt salt solution, and the manganese salt solution is water.

[0247] The complexing agent is a compound that can form a complex with nickel ions, cobalt ions and manganese ions in an aqueous solution. Examples of the complexing agent include ammonium ion donors, hydrazine, ethylenediaminetetraacetic acid, nitrilotriacetic acid, uracil diacetic acid and glycine. Examples of the ammonium ion donor include ammonium hydroxide, ammonium sulfate, ammonium chloride, ammonium carbonate, ammonium fluoride and other ammonium salts.

[0248] In the manufacturing process of the metal composite hydroxide, a complexing agent may or may not be used. When a complexing agent is used, the amount of the complexing agent contained in the mixed solution comprising a nickel salt solution, an arbitrary metal salt solution and a complexing agent is, for example, a molar ratio relative to the total number of moles of the metal salt greater than 0 and less than 2.0.

[0249] The amount of the complexing agent contained in the mixed solution including the nickel salt solution, the cobalt salt solution, the manganese salt solution and the complexing agent is, for example, greater than 0 and 2.0 or less in terms of molar ratio relative to the total number of moles of the metal salts.

[0250] In the coprecipitation method, in order to adjust the pH of the mixed solution containing the nickel salt solution, the optional metal salt solution and the complexing agent, an alkali metal hydroxide is added to the mixed solution before the pH of the mixed solution changes from alkaline to neutral. The alkali metal hydroxide is, for example, sodium hydroxide or potassium hydroxide.

[0251] In addition, the pH value in this specification is defined as a value measured when the temperature of the mixed solution is 40° C. The pH of the mixed solution is measured when the temperature of the mixed solution sampled from the reaction tank reaches 40° C.

[0252] If a complexing agent is continuously supplied to the reaction tank in addition to the above-mentioned nickel salt solution, cobalt salt solution and manganese salt solution, Ni, Co and Mn react to generate Ni (1-y-z) Co y Mn z (OH)2.

[0253] During the reaction, the temperature of the reaction tank is controlled within the range of, for example, 20° C. to 80° C., preferably 30° C. to 70° C.

[0254] During the reaction, the pH value in the reaction tank is controlled within the range of, for example, pH 9 or higher and pH 13 or lower, preferably pH 11 or higher and pH 13 or lower.

[0255] The contents in the reaction tank are stirred and mixed appropriately.

[0256] The reaction tank used in the continuous coprecipitation method may be a type of reaction tank that overflows in order to separate the formed reaction precipitate.

[0257] By appropriately controlling the metal salt concentration of the metal salt solution supplied to the reaction tank, the reaction temperature, the reaction pH, the calcination conditions described below, and the like, various physical properties of the finally obtained positive electrode active material can be controlled.

[0258] In addition to the control of the above conditions, various gases, such as inert gases such as nitrogen, argon, and carbon dioxide, oxidizing gases such as air and oxygen, or mixed gases thereof may be supplied into the reaction vessel to control the oxidation state of the obtained reaction product.

[0259] As the compound (oxidizing agent) for oxidizing the obtained reaction product, peroxides such as hydrogen peroxide, peroxide salts such as permanganate, perchlorates, hypochlorites, nitric acid, halogens, ozone, and the like can be used.

[0260] As the compound for reducing the obtained reaction product, an organic acid such as oxalic acid and formic acid, a sulfite, hydrazine, or the like can be used.

[0261] Specifically, the reaction tank may be in an inactive atmosphere. If the reaction tank is in an inactive atmosphere, the metals contained in the mixed solution that are more easily oxidized than Ni can be suppressed from agglomerating before Ni. Therefore, a uniform metal composite hydroxide can be obtained.

[0262] In addition, the reaction tank may be in a moderate oxidizing atmosphere. The oxidizing atmosphere may be an oxygen-containing atmosphere in which an oxidizing gas is mixed with an inert gas, or an oxidant may be present under an inert gas atmosphere. By making the reaction tank in a moderate oxidizing atmosphere, the transition metal contained in the mixed solution is moderately oxidized, and the morphology of the metal composite oxide becomes easy to control.

[0263] The oxygen or oxidant in the oxidizing atmosphere may contain enough oxygen atoms to oxidize the transition metal.

[0264] When the oxidizing atmosphere is an oxygen-containing atmosphere, the atmosphere in the reaction vessel can be controlled by a method such as introducing an oxidizing gas into the reaction vessel or bubbling the oxidizing gas in the mixed liquid.

[0265] After the above reaction, the obtained reaction precipitate is washed with water and then dried to obtain a metal composite compound. In this embodiment, nickel cobalt manganese hydroxide is obtained as the metal composite compound.

[0266] Furthermore, when impurities derived from the mixed solution remain when the reaction precipitate is washed with water alone, the reaction precipitate may be washed with weak acid water or an alkaline solution as required. Examples of the alkaline solution include aqueous solutions containing sodium hydroxide and potassium hydroxide.

[0267] By applying an appropriate external force to the dried metal composite compound to pulverize it and adjust the dispersion state of the particles, it is possible to obtain the above L 003 And the metal composite compound whose BET specific surface area is controlled within the range of this embodiment.

[0268] "Appropriate external force" refers to an external force that disperses the condensed state without destroying the crystallites of the metal composite compound. In the present embodiment, during the above-mentioned pulverization, a grinding mill is preferably used as a pulverizer, and a stone mill type grinding mill is particularly preferred. When a stone mill type grinding mill is used, the spacing between the upper mill and the lower mill is preferably adjusted according to the condensed state of the metal composite hydroxide. The spacing between the upper mill and the lower mill is preferably in the range of, for example, 10 μm or more and 200 μm or less.

[0269] It should be noted that, in the above-mentioned examples, a nickel-cobalt-manganese composite hydroxide was produced, but a nickel-cobalt-manganese composite oxide may also be produced.

[0270] For example, a nickel-cobalt-manganese composite oxide can be produced by oxidizing a nickel-cobalt-manganese composite hydroxide.

[0271] (Process for producing lithium metal composite oxide)

[0272] In this step, after the metal composite oxide or metal composite hydroxide is dried, the metal composite oxide or metal composite hydroxide is mixed with a lithium compound.

[0273] Furthermore, in the present embodiment, when the metal composite oxide or metal composite hydroxide and the lithium compound are mixed, it is preferred that an inactive flux is mixed at the same time.

[0274] The mixture of the metal composite compound and the lithium compound is fired in the presence of the inactive flux by firing a mixture containing a metal composite oxide, a lithium compound and an inactive flux or a mixture containing a metal composite hydroxide, a lithium compound and an inactive flux.

[0275] By calcining the mixture of the metal composite compound and the lithium compound in the presence of an inactive flux, it is difficult to generate secondary particles formed by sintering primary particles together. In addition, the growth of single particles can be promoted.

[0276] As the lithium compound, any one of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium hydroxide, lithium oxide, lithium chloride, and lithium fluoride can be used, or a mixture of two or more thereof can be used. Among them, any one or both of lithium hydroxide and lithium carbonate are preferred.

[0277] When the lithium hydroxide contains lithium carbonate as an impurity, the content of lithium carbonate in the lithium hydroxide is preferably 5% by mass or less.

[0278] The drying conditions of the metal composite oxide or metal composite hydroxide are not particularly limited. The drying conditions may be, for example, any one of the following conditions 1) to 3).

[0279] 1) Conditions under which the metal composite oxide or metal composite hydroxide is not oxidized or reduced. Specifically, these are drying conditions under which the oxide remains in the state of an oxide, and drying conditions under which the hydroxide remains in the state of a hydroxide.

[0280] 2) Conditions for oxidation of the metal composite hydroxide: Specifically, these are dry conditions for oxidation of the hydroxide to oxide.

[0281] 3) Conditions under which the metal composite oxide is reduced. Specifically, these are drying conditions under which the oxide is reduced to a hydroxide.

[0282] In order to set the conditions to prevent oxidation or reduction, an inert gas such as nitrogen, helium, or argon may be used as the atmosphere during drying.

[0283] In order to set the conditions under which the hydroxide is oxidized, oxygen or air may be used as the atmosphere during drying.

[0284] Furthermore, in order to set the conditions under which the metal composite oxide is reduced, a reducing agent such as hydrazine or sodium sulfite may be used in an inert gas atmosphere during drying.

[0285] The metal composite oxide or metal composite hydroxide may be appropriately classified after being dried.

[0286] The above lithium compounds and metal composite compounds are used in consideration of the composition ratio of the final target. For example, in the case of using a nickel-cobalt-manganese composite compound, the lithium compound and the metal composite compound are mixed in an amount of Li[Li x (Ni (1-y-z) Co y Mn z ) 1-x ]The ratio corresponding to the composition ratio of O2 is used.

[0287] When Li is excessive (containing molar ratio exceeding 1) in the lithium metal composite oxide, the lithium compound and the metal element contained in the metal composite compound are mixed in a ratio exceeding 1 in molar ratio.

[0288] The lithium-nickel-cobalt-manganese composite oxide is obtained by calcining a mixture of the nickel-cobalt-manganese composite compound and the lithium compound. It should be noted that dry air, oxygen atmosphere, inert atmosphere, etc. are used during calcination according to the desired composition, and multiple calcination steps can be performed if necessary.

[0289] In this embodiment, the mixture may be fired in the presence of an inactive flux. By firing in the presence of an inactive flux, the reaction of the mixture can be accelerated.

[0290] The inactive flux may remain in the fired lithium metal composite oxide, or may be removed by washing with water or alcohol after firing. The fired lithium metal composite oxide is preferably washed with water or alcohol.

[0291] By adjusting the holding temperature during calcination, the particle size of the single particle can be controlled within a preferred range of the present embodiment.

[0292] Generally, the higher the holding temperature, the larger the particle size of the single particle and the smaller the BET specific surface area. The holding temperature during calcination can be appropriately adjusted according to the type and amount of the transition metal element, precipitant, and inactive flux used.

[0293] The holding temperature may be set in consideration of the melting point of the inactive flux described below, and is preferably set within a range of [melting point of the inactive flux - 200°C] or higher and [melting point of the inactive flux + 200°C] or lower.

[0294] Specifically, the holding temperature is in the range of 200°C to 1150°C, preferably 300°C to 1050°C, and more preferably 500°C to 1000°C.

[0295] In addition, the time maintained at the above-mentioned holding temperature can be listed as more than 0.1 hour and less than 20 hours, preferably more than 0.5 hour and less than 10 hours. The heating rate to the above-mentioned holding temperature is usually more than 50°C / hour and less than 400°C / hour, and the cooling rate from the above-mentioned holding temperature to room temperature is usually more than 10°C / hour and less than 400°C / hour. In addition, as the atmosphere for sintering, air, oxygen, nitrogen, argon or a mixed gas thereof can be used.

[0296] In addition, in order to 003 To control the direction to be small, the material containing the above-mentioned impurity atoms can be added to the mixed solution (containing a mixed solution of nickel salt solution, any metal salt solution and a complexing agent) in the precursor manufacturing process (during coprecipitation synthesis), or it can be added when mixing with the lithium compound.

[0297] As materials containing impurity atoms, FeCO3, CuCO3, CrCO3, CaCO3, MgCO3, Na2CO3, FeSO4, CuSO4, Cr2(SO4)3, CaSO4, MgSO4, Na2SO4, etc. can be listed.

[0298] The amount of the material containing the impurity atoms added may be adjusted within a range of 0.01 parts by mass or more and 1.00 parts by mass based on 100 parts by mass of the metal composite oxide or metal composite hydroxide.

[0299] The lithium metal composite oxide obtained by calcination is crushed and then appropriately classified to prepare a positive electrode active material suitable for all-solid-state lithium ion batteries.

[0300] By applying an appropriate external force to the lithium metal composite oxide obtained by calcination to pulverize it and adjusting the dispersion state of the particles, a positive electrode active material satisfying the above-mentioned requirements (2) and (3) can be obtained.

[0301] "Appropriate external force" refers to an external force that disperses the condensed state without destroying the microcrystals of the positive electrode active material. In the present embodiment, during the above-mentioned pulverization, a grinding mill is preferably used as a pulverizer, and a stone mill type grinding mill is particularly preferred. When a stone mill type grinding mill is used, the spacing between the upper mill and the lower mill is preferably adjusted according to the condensed state of the lithium metal composite oxide. The spacing between the upper mill and the lower mill is preferably in the range of 10 μm or more and 200 μm or less, for example.

[0302] In this embodiment, it is preferable to use an inactive flux having a small amount of impurity atoms.

[0303] Specifically, the total amount of impurity atoms measured by the method described below is preferably 0.001% or more and 0.050% or less.

[0304] <Method for Determining the Atomic Weight of Impurities in Inactive Flux>

[0305] First, the powder of the inactive flux is dissolved in hydrochloric acid.

[0306] Next, the mass fractions of K atoms, S atoms, Fe atoms, Cr atoms, Cu atoms, Ca atoms, Mg atoms, and Na atoms contained in the inert flux powder were analyzed and calculated using an inductively coupled plasma atomic emission spectrometer (ICP-AES).

[0307] Next, the sum of the mass fractions of impurity atoms (K atoms, Fe atoms, Cr atoms, Cu atoms, Ca atoms, Mg atoms, and Na atoms) is calculated to measure the total amount of impurity atoms.

[0308] As the inductively coupled plasma emission spectrometry analyzer, for example, SPS3000 manufactured by SII NanoTechnology Co., Ltd. can be used.

[0309] When an inactive flux having a sum of mass fractions of impurity atoms equal to or greater than the above lower limit is used, a positive electrode active material in which excessive crystal growth is suppressed can be easily obtained.

[0310] When an inactive flux having a sum of mass fractions of impurity atoms of not more than the above upper limit is used, a positive electrode active material having a small amount of impurity atoms that may serve as resistance during charge and discharge can be easily obtained.

[0311] As the inactive flux having the sum of the mass fractions of impurity atoms being equal to or less than the above upper limit, a high-purity commercial product can be used. Examples of the high-purity commercial product include special-grade reagents from Fujifilm Wako Pure Chemical Industries, Ltd.

[0312] In addition, the purity of the inactive flux can be increased by recrystallization, and the sum of the mass fractions of impurity atoms can be adjusted to be below the above upper limit. Specifically, crystals containing impurities are dissolved in a solvent, and high-purity crystals are precipitated by utilizing the evaporation of the solvent, the difference in solubility caused by the temperature difference or the change in the mixing ratio of the solvent.

[0313] In the present embodiment, it is preferable to use a commercially available high-purity inactive flux.

[0314] The inactive flux is not particularly limited as long as it is an inactive flux that is difficult to react with the mixture during firing. In the present embodiment, the inactive flux may include fluorides of one or more elements (hereinafter referred to as "A") selected from the group consisting of Na, K, Rb, Cs, Ca, Mg, Sr and Ba, chlorides of A, carbonates of A, sulfates of A, nitrates of A, phosphates of A, hydroxides of A, molybdates of A and tungstates of A.

[0315] As fluorides of A, there can be listed NaF (melting point: 993°C), KF (melting point: 858°C), RbF (melting point: 795°C), CsF (melting point: 682°C), CaF2 (melting point: 1402°C), MgF2 (melting point: 1263°C), SrF2 (melting point: 1473°C) and BaF2 (melting point: 1355°C).

[0316] As chlorides of A, there can be listed NaCl (melting point: 801°C), KCl (melting point: 770°C), RbCl (melting point: 718°C), CsCl (melting point: 645°C), CaCl2 (melting point: 782°C), MgCl2 (melting point: 714°C), SrCl2 (melting point: 857°C) and BaCl2 (melting point: 963°C).

[0317] As carbonates of A, there can be listed Na2CO3 (melting point: 854°C), K2CO3 (melting point: 899°C), Rb2CO3 (melting point: 837°C), Cs2CO3 (melting point: 793°C), CaCO3 (melting point: 825°C), MgCO3 (melting point: 990°C), SrCO3 (melting point: 1497°C) and BaCO3 (melting point: 1380°C).

[0318] As sulfates of A, there are Na2SO4 (melting point: 884°C), K2SO4 (melting point: 1069°C), Rb2SO4 (melting point: 1066°C), Cs2SO4 (melting point: 1005°C), CaSO4 (melting point: 1460°C), MgSO4 (melting point: 1137°C), SrSO4 (melting point: 1605°C) and BaSO4 (melting point: 1580°C).

[0319] Examples of the nitrate of A, the phosphate of A, the hydroxide of A, the molybdate of A, and the tungstate of A include compounds described in Japanese Patent No. 6734491B.

[0320] In the present embodiment, two or more of these inert fluxes may be used. When two or more of these inert fluxes are used, the melting point of the entire inert flux may decrease.

[0321] Among these inactive fluxes, one or more salts selected from the group consisting of carbonates of A, sulfates of A, and chlorides of A are preferred as an inactive flux for obtaining a lithium metal composite oxide having higher crystallinity.

[0322] Furthermore, A is preferably any one or both of Na and K.

[0323] That is, among the above-mentioned inactive fluxes, particularly preferred inactive fluxes are preferably one or more selected from the group consisting of NaCl, KCl, Na2CO3, K2CO3, Na2SO4 and K2SO4, and more preferably, any one or both of K2SO4 and Na2SO4 are used.

[0324] The amount of the inactive flux present during calcination may be appropriately selected. As an example, the amount of the inactive flux present during calcination is preferably 0.1 parts by mass or more, and more preferably 1 part by mass or more, based on 100 parts by mass of the lithium compound.

[0325] In addition, when promoting crystal growth, an inactive flux other than the above-mentioned inactive flux may be used in combination. Examples of such inactive flux include ammonium salts such as NH4Cl and NH4F.

[0326] (Clad Layer Formation Step)

[0327] When forming a coating layer on the surface of a lithium metal composite oxide, firstly, a coating material raw material and a lithium metal composite oxide are mixed, and then, if necessary, heat treatment is performed to form a coating layer composed of a metal composite oxide on the surface of the lithium metal composite oxide particles.

[0328] As the method for forming the coating layer and the coating material material in the present embodiment, the method and the coating material material described in Japanese Patent No. 673441B can be applied.

[0329] The particles having the coating layer formed on the surface of the lithium metal composite oxide are appropriately crushed and classified to obtain a positive electrode active material for an all-solid-state lithium ion battery.

[0330] <Method 2 for producing positive electrode active material>

[0331] When the positive electrode active material of the present embodiment includes single particles and secondary particles, the positive electrode active material can be produced by making the following changes to the above-mentioned method 1 for producing a positive electrode active material.

[0332] (Metal Composite Compound Manufacturing Process)

[0333] In the manufacturing method 2 of the positive electrode active material, the metal composite compound that eventually forms a single particle and the metal composite compound that forms secondary particles are respectively manufactured in the manufacturing process of the metal composite compound. Hereinafter, the metal composite compound that eventually forms a single particle is sometimes described as a "single particle precursor". In addition, the metal composite compound that eventually forms secondary particles is sometimes described as a "secondary particle precursor".

[0334] In the method 2 for producing a positive electrode active material, when producing a metal composite compound by the above-mentioned coprecipitation method, a first coprecipitation tank for producing a single particle precursor and a second coprecipitation tank for forming a secondary particle precursor are used.

[0335] The single particle precursor can be produced by appropriately controlling the concentration of the metal salt supplied to the first coprecipitation tank, the stirring speed, the reaction temperature, the reaction pH, the calcination conditions described below, and the like.

[0336] Specifically, the temperature of the reaction tank is preferably, for example, 30° C. or higher and 80° C. or lower, more preferably controlled within the range of 40° C. or higher and 70° C. or lower, and further preferably within the range of ±20° C. relative to the second reaction tank described later. In addition, the pH value in the reaction tank is preferably, for example, pH 10 or higher and pH 13 or lower, more preferably controlled within the range of pH 11 or higher and pH 12.5 or lower, further preferably within the range of ±pH 2 relative to the second reaction tank described later, and particularly preferably a pH higher than that of the second reaction tank.

[0337] Furthermore, by appropriately controlling the concentration of the metal salt supplied to the second coprecipitation tank, the stirring speed, the reaction temperature, the reaction pH, the calcination conditions described below, and the like, the secondary particle precursor can be produced.

[0338] Specifically, the temperature of the reaction tank is preferably, for example, 20° C. or higher and 80° C. or lower, more preferably controlled within the range of 30° C. or higher and 70° C. or lower, and further preferably within the range of ±20° C. relative to the second reaction tank described later. In addition, the pH value in the reaction tank is preferably, for example, pH 10 or higher and pH 13 or lower, more preferably controlled within the range of pH 11 or higher and pH 12.5 or lower, further preferably within the range of ±pH 2 relative to the second reaction tank described later, and particularly preferably a pH lower than that of the second reaction tank.

[0339] The reaction products thus obtained are washed with water and then dried to isolate the nickel-cobalt-manganese composite hydroxide. The isolated nickel-cobalt-manganese composite hydroxide includes a single particle precursor and a secondary particle precursor.

[0340] It should be noted that, in the above examples, nickel-cobalt-manganese composite hydroxides are produced, but nickel-cobalt-manganese composite oxides can also be produced. For example, nickel-cobalt-manganese composite oxides can be produced by calcining nickel-cobalt-manganese composite hydroxides. The calcining conditions of nickel-cobalt-manganese composite hydroxides can be the above conditions.

[0341] (Process for producing lithium metal composite oxide)

[0342] In the production process of lithium metal composite oxide, the metal composite oxide or metal composite hydroxide obtained as a single particle precursor or secondary particle precursor in the above process is dried and then mixed with a lithium compound. The single particle precursor or secondary particle precursor may be appropriately classified after drying.

[0343] By mixing the single particle precursor and the secondary particle precursor at a predetermined mass ratio during mixing, the abundance ratio of the obtained single particles and secondary particles can be roughly controlled.

[0344] It should be noted that, in the process after mixing, the single particle precursor and the secondary particle precursor are condensed or separated respectively, and the secondary particles generated by the condensation of the single particle precursor and the single particles generated by the separation of the secondary particle precursor can also exist respectively. By adjusting the mixing ratio of the single particle precursor and the secondary particle precursor and the conditions of the process after mixing, the existence ratio of the single particle and the secondary particle in the finally obtained positive electrode active material can be controlled.

[0345] By adjusting the holding temperature during calcination, the average particle size of the single particles of the obtained positive electrode active material and the average particle size of the secondary particles can be controlled within the preferred range of the present embodiment.

[0346] <Method for producing positive electrode active material 3>

[0347] In addition, when the positive electrode active material of this embodiment includes single particles and secondary particles, the first positive electrode active material composed of single particles and the second positive electrode active material composed of secondary particles can be manufactured separately by the above-mentioned positive electrode active material manufacturing method 1 and the first positive electrode active material and the second positive electrode active material can be mixed for manufacturing.

[0348] In the manufacturing method 3 of the positive electrode active material, in the manufacturing process of the lithium metal composite oxide, it is preferable that the holding temperature when the lithium metal composite oxide contained in the first positive electrode active material is calcined is higher than the holding temperature when the lithium metal composite oxide contained in the second positive electrode active material is calcined. Specifically, when manufacturing the lithium metal composite oxide contained in the first positive electrode active material, the holding temperature is preferably 30° C. or more higher than the holding temperature of the lithium metal composite oxide contained in the second positive electrode active material, more preferably 50° C. or more higher, and further preferably 80° C. or more higher.

[0349] By mixing the obtained first positive electrode active material and second positive electrode active material at a predetermined ratio, a positive electrode active material including single particles and secondary particles can be obtained.

[0350] <All-solid-state lithium-ion battery>

[0351] Next, while describing the structure of the all-solid-state lithium-ion battery, a positive electrode using an all-solid-state lithium-ion battery positive electrode active material of one embodiment of the present invention as a positive electrode active material of the all-solid-state lithium-ion battery and an all-solid-state lithium-ion battery having the positive electrode are described. The all-solid-state lithium-ion battery of this embodiment is a secondary battery.

[0352] Figure 1 , 2 This is a schematic diagram showing an example of an all-solid-state lithium-ion battery according to the present embodiment. Figure 1 This is a schematic diagram showing a stacked body included in the all-solid-state lithium-ion battery of the present embodiment. Figure 2 Schematic diagram showing the overall structure of the all-solid-state lithium-ion battery of this embodiment.

[0353] The all-solid-state lithium-ion battery 1000 includes a laminate 100 including a positive electrode 110 , a negative electrode 120 , and a solid electrolyte layer 130 , and an outer casing 200 that accommodates the laminate 100 .

[0354] The materials constituting each member are described below.

[0355] The laminate 100 may include an external terminal 113 connected to the positive electrode current collector 112 and an external terminal 123 connected to the negative electrode current collector 122 .

[0356] In the stack 100, the positive electrode 110 and the negative electrode 120 sandwich the solid electrolyte layer 130 in a manner that does not cause a short circuit between them. In addition, the all-solid-state lithium ion battery 1000 may also have a separator such as that used in existing liquid lithium ion secondary batteries between the positive electrode 110 and the negative electrode 120 to prevent a short circuit between the positive electrode 110 and the negative electrode 120.

[0357] The all-solid lithium ion battery 1000 includes an insulator (not shown) that insulates the stacked body 100 from the outer casing 200 , and a sealing body (not shown) that seals the opening 200 a of the outer casing 200 .

[0358] The outer package 200 may be formed of a metal material having high corrosion resistance, such as aluminum, stainless steel, or nickel-plated steel. Alternatively, a container formed of a laminate film having at least one surface subjected to corrosion resistance treatment and processed into a bag shape may be used.

[0359] Examples of the shape of the all-solid-state lithium-ion battery 1000 include a coin shape, a button shape, a paper shape (or a sheet shape), a cylindrical shape, and a square shape.

[0360] The all-solid-state lithium ion battery 1000 is shown as having one stack 100 , but is not limited thereto. The all-solid-state lithium ion battery 1000 may be configured such that the stack 100 is used as a single cell and a plurality of cells (stacks 100 ) are sealed inside an outer casing 200 .

[0361] Hereinafter, each configuration will be described in sequence.

[0362] (positive electrode)

[0363] The positive electrode 110 includes a positive electrode active material layer 111 and a positive electrode current collector 112 .

[0364] The positive electrode active material layer 111 contains the positive electrode active material as one embodiment of the present invention described above. In addition, the positive electrode active material layer 111 may contain a solid electrolyte (second solid electrolyte), a conductive material, and a binder.

[0365] The positive electrode active material contained in the positive electrode active material layer 111 is in contact with the second solid electrolyte contained in the positive electrode active material layer 111. In detail, the positive electrode active material layer 111 includes: a plurality of particles (positive electrode active material) containing crystals of a lithium metal composite oxide and a solid electrolyte filled between the plurality of particles (positive electrode active material) and in contact with the particles (positive electrode active material).

[0366] (Solid Electrolyte)

[0367] As a solid electrolyte that the positive electrode active material layer 111 may have, a solid electrolyte having lithium ion conductivity and used in a known all-solid-state battery may be used. As such a solid electrolyte, inorganic electrolytes and organic electrolytes may be cited. As inorganic electrolytes, oxide-based solid electrolytes, sulfide-based solid electrolytes, and hydride-based solid electrolytes may be cited. As organic electrolytes, polymer-based solid electrolytes may be cited.

[0368] In the present embodiment, an oxide-based solid electrolyte or a sulfide-based solid electrolyte is preferably used, and an oxide-based solid electrolyte is more preferably used.

[0369] (Oxide-based solid electrolyte)

[0370] Examples of the oxide-based solid electrolyte include perovskite-type oxides, NASICON-type oxides, LISICON-type oxides, and garnet-type oxides.

[0371] Examples of perovskite-type oxides include Li a La 1-a Li-La-Ti oxides such as TiO3 (0<a<1), Li b La 1-b Li-La-Ta oxides such as TaO3 (0<b<1), Li c La 1-c Li-La-Nb oxides such as NbO3 (0<c<1), etc.

[0372] Examples of NASICON-type oxides include Li 1+d Al d Ti 2-d (PO4)3(0≤d≤1), etc. NASICON-type oxides are based on Li m M 1 n M 2 o P p O q Represents oxide.

[0373] Where M 1 It is one or more elements selected from the group consisting of B, Al, Ga, In, C, Si, Ge, Sn, Sb and Se.

[0374] Where M 2 It is one or more elements selected from the group consisting of Ti, Zr, Ge, In, Ga, Sn and Al.

[0375] Wherein, m, n, o, p and q are any positive numbers.

[0376] As LISICON type oxides, Li4M 3 O4-Li3M 4 Oxide represented by O4, etc.

[0377] Where M 3 It is one or more elements selected from the group consisting of Si, Ge, and Ti.

[0378] Where M 4 It is one or more elements selected from the group consisting of P, As and V.

[0379] As garnet-type oxides, Li7La3Zr2O 12 (LLZ) and other Li-La-Zr oxides.

[0380] The oxide-based solid electrolyte may be a crystalline material or an amorphous material. Examples of amorphous solid electrolytes include Li-BO compounds such as Li3BO3, Li2B4O7, and LiBO2. The oxide-based solid electrolyte preferably includes an amorphous material.

[0381] (Sulfide-based solid electrolyte)

[0382] As sulfide-based solid electrolytes, there are listed Li2S-P2S5 compounds, Li2S-SiS2 compounds, Li2S-GeS2 compounds, Li2S-B2S3 compounds, Li2S-P2S3 compounds, LiI-Si2S-P2S5 compounds, LiI-Li2S-P2O5 compounds, LiI-Li3PO4-P2S5 compounds, Li 10 GeP2S 12 wait.

[0383] It should be noted that in this specification, the expression "system compound" referring to a sulfide-based solid electrolyte is used as a general term for solid electrolytes that mainly include raw materials such as "Li2S" and "P2S5" described before the "system compound". For example, the Li2S-P2S5 system compound contains Li2S and P2S5 and further includes solid electrolytes containing other raw materials. In addition, the Li2S-P2S5 system compound also includes solid electrolytes in which the mixing ratio of Li2S and P2S5 is different.

[0384] Examples of Li2S-P2S5 compounds include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-Z m S n (m and n are positive numbers. Z is Ge, Zn or Ga), etc.

[0385] As Li2S-SiS2 compounds, there are Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li2SO4, Li2S-SiS2-Li x MO y (x and y are positive numbers. M is P, Si, Ge, B, Al, Ga or In), etc.

[0386] Examples of Li2S-GeS2 compounds include Li2S-GeS2, Li2S-GeS2-P2S5, and the like.

[0387] The sulfide-based solid electrolyte may be a crystalline material or an amorphous (amorphous) material. The sulfide-based solid electrolyte preferably includes an amorphous material.

[0388] (Hydride-based solid electrolyte)

[0389] As hydride-based solid electrolyte materials, there can be listed LiBH4, LiBH4-3KI, LiBH4-PI2, LiBH4-P2S5, LiBH4-LiNH2, 3LiBH4-LiI, LiNH2, Li2AlH6, Li(NH2)2I, Li2NH, LiGd(BH4)3Cl, Li2(BH4)(NH2), Li3(NH2)I, Li4(BH4)(NH2)3, etc.

[0390] Examples of the polymer solid electrolyte include organic polymer electrolytes such as polyethylene oxide-based polymer compounds and polymer compounds containing one or more selected from the group consisting of polyorganosiloxane chains and polyoxyalkylene chains.

[0391] In addition, a so-called gel-type electrolyte in which a non-aqueous electrolyte is retained in a polymer compound may also be used. The non-aqueous electrolyte possessed by the gel-type polymer-based solid electrolyte is different from the non-aqueous electrolyte possessed by the existing liquid-based lithium-ion secondary battery, and loses fluidity and exhibits a higher rigidity modulus than the electrolyte. The rigidity modulus of the electrolyte used in the liquid-based lithium-ion secondary battery is zero. In this regard, the lithium-ion secondary battery using a gel-type polymer-based solid electrolyte is also different from the existing liquid-based lithium-ion secondary battery, and is equivalent to the all-solid-state lithium-ion battery of the present invention.

[0392] In the gel-type polymer-based solid electrolyte, the ratio of the polymer compound contained in the solid electrolyte layer is preferably 1 mass % or more and 50 mass % or less.

[0393] Two or more solid electrolytes may be used in combination within a range not impairing the effects of the invention.

[0394] (Conductive materials)

[0395] As conductive materials that the positive electrode active material layer 111 of the present embodiment may have, carbon materials and metal compounds can be used. As carbon materials, graphite powder, carbon black (such as acetylene black), fibrous carbon materials, etc. can be listed. Since carbon black is a particle and has a large surface area, by adding an appropriate amount to the positive electrode active material layer 111, the internal conductivity of the positive electrode 110 can be improved, and the charge and discharge efficiency and output characteristics can be improved. On the other hand, if the amount of carbon black added is too much, the bonding force between the positive electrode active material layer 111 and the positive electrode collector 112 and the bonding force inside the positive electrode active material layer 111 are reduced, which becomes a cause of increasing the internal resistance. As metal compounds, conductive metals, metal alloys, and metal oxides can be listed.

[0396] The proportion of the conductive material in the positive electrode active material layer 111 is preferably 5 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the positive electrode active material in the case of a carbon material. This proportion can also be reduced when a fibrous carbon material such as graphitized carbon fiber or carbon nanotube is used as the conductive material.

[0397] (Adhesive)

[0398] When the positive electrode active material layer 111 has a binder, a thermoplastic resin can be used as the binder. Examples of the thermoplastic resin include polyimide resins, fluororesins, polyolefin resins, and fiber resins.

[0399] Examples of the fluororesin include polyvinylidene fluoride, polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers, hexafluoropropylene-vinylidene fluoride copolymers, and tetrafluoroethylene-perfluorovinyl ether copolymers.

[0400] Hereinafter, polyvinylidene fluoride may be referred to as PVdF.

[0401] Examples of the polyolefin resin include polyethylene and polypropylene.

[0402] Examples of the fiber-based resin include ethyl cellulose, acetyl cellulose, and nitrocellulose.

[0403] These thermoplastic resins may be mixed and used in combination of two or more. By using fluororesin and polyolefin resin as binders and setting the ratio of fluororesin to the entire positive electrode active material layer 111 to be 1% by mass or more and 10% by mass or less, and setting the ratio of polyolefin resin to be 0.1% by mass or more and 2% by mass or less, a positive electrode active material layer 111 having high adhesion between the positive electrode active material layer 111 and the positive electrode current collector 112 and high bonding strength inside the positive electrode active material layer 111 is obtained.

[0404] The positive electrode active material layer 111 may also be processed in advance into a sheet-shaped molded body containing a positive electrode active material and used as an "electrode" in the present invention. In addition, in the following description, such a sheet-shaped molded body is sometimes referred to as a "positive electrode active material sheet". A laminated body in which a collector is laminated on a positive electrode active material sheet may also be used as an electrode.

[0405] The positive electrode active material sheet may contain at least one selected from the group consisting of the above-mentioned solid electrolyte, conductive material and binder.

[0406] The positive electrode active material sheet is obtained by, for example, mixing the positive electrode active material, the sintering aid, the above-mentioned conductive material, the above-mentioned binder, a plasticizer, and a solvent to prepare a slurry, applying the obtained slurry on a carrier film, and drying it.

[0407] As the sintering aid, for example, Li 3 BO 3 or Al 2 O 3 can be used.

[0408] As the plasticizer, for example, dioctyl phthalate can be used.

[0409] As the solvent, for example, acetone, ethanol, or N-methyl-2-pyrrolidone can be used.

[0410] When preparing the slurry, a ball mill can be used for mixing. Since the obtained mixture mostly contains bubbles mixed in during mixing, it is appropriate to degas by reducing pressure. If degassing is performed, a part of the solvent evaporates and concentrates, thereby making the slurry high in viscosity.

[0411] The slurry can be applied using a known doctor blade.

[0412] As the carrier film, a PET film can be used.

[0413] The positive electrode active material sheet obtained after drying is peeled from the support film and processed into a desired shape by appropriate punching before use. Alternatively, the positive electrode active material sheet may be uniaxially pressed in the thickness direction as appropriate.

[0414] (Positive electrode collector)

[0415] A sheet-shaped member formed of a metal material such as Al, Ni, stainless steel, or Au can be used as the positive electrode current collector 112 of the positive electrode 110. Among them, a positive electrode current collector formed of Al and processed into a thin film is preferred because it is easy to process and inexpensive.

[0416] As a method for supporting the positive electrode active material layer 111 on the positive electrode current collector 112, there is a method of press-molding the positive electrode active material layer 111 on the positive electrode current collector 112. The press-molding may be performed by cold pressing or hot pressing.

[0417] In addition, a positive electrode mixture can also be prepared by using an organic solvent to gelatinize a mixture of a positive electrode active material, a solid electrolyte, a conductive material, and a binder, and the obtained positive electrode mixture is applied to at least one side of the positive electrode collector 112 and dried, pressed and adhered, thereby supporting the positive electrode active material layer 111 on the positive electrode collector 112.

[0418] Alternatively, a positive electrode mixture may be prepared by pasting a mixture of a positive electrode active material, a solid electrolyte, and a conductive material using an organic solvent, and the obtained positive electrode mixture may be applied to at least one side of the positive electrode collector 112 and dried and sintered, thereby supporting the positive electrode active material layer 111 on the positive electrode collector 112 .

[0419] Examples of the organic solvent that can be used for the positive electrode mixture include amine solvents, ether solvents, ketone solvents, ester solvents, and amide solvents.

[0420] Examples of the amine solvent include N,N-dimethylaminopropylamine and diethylenetriamine.

[0421] Examples of the ether solvent include tetrahydrofuran.

[0422] Examples of the ketone solvent include methyl ethyl ketone.

[0423] Examples of the ester solvent include methyl acetate.

[0424] Examples of the amide solvent include dimethylacetamide and N-methyl-2-pyrrolidone. Hereinafter, N-methyl-2-pyrrolidone may be referred to as NMP.

[0425] Examples of a method for applying the positive electrode mixture to the positive electrode current collector 112 include slot die coating, screen coating, curtain coating, doctor blade coating, gravure coating, and electrostatic spraying.

[0426] The positive electrode 110 may be manufactured by the methods listed above.

[0427] (negative electrode)

[0428] The negative electrode 120 includes a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 includes a negative electrode active material. In addition, the negative electrode active material layer 121 may also include a solid electrolyte and a conductive material. The solid electrolyte, conductive material, and binder may be those described above.

[0429] (Negative electrode active material)

[0430] Examples of the negative electrode active material contained in the negative electrode active material layer 121 include carbon materials, chalcogenides (oxides, sulfides, etc.), nitrides, metals, or alloys that can be doped and dedoped with lithium ions at a potential lower than that of the positive electrode 110 .

[0431] Examples of carbon materials that can be used as the negative electrode active material include graphites such as natural graphite and artificial graphite, cokes, carbon black, pyrolytic carbons, carbon fibers, and calcined products of organic polymer compounds.

[0432] Examples of oxides that can be used as the negative electrode active material include the following.

[0433] ·SiO2、SiO equationSiO x (wherein x is a positive real number) is an oxide of silicon represented by.

[0434] ·TiO2、TiO equationTiO x (wherein x is a positive real number).

[0435] ·V2O5、VO2 equation VO x (wherein x is a positive real number).

[0436] ·Fe3O4, Fe2O3, FeO equation x (wherein x is a positive real number) is an iron oxide represented by.

[0437] SnO2, SnO equation SnO x (wherein x is a positive real number) is an oxide of tin represented by.

[0438] WO3, WO2 and other general formula WO x(wherein x is a positive real number) is an oxide of tungsten represented by.

[0439] ·Li4Ti5O 12 , LiVO2 and other metal composite oxides containing lithium and titanium or vanadium.

[0440] Examples of sulfides that can be used as the negative electrode active material include the following.

[0441] Ti2S3, TiS2, TiS equation TiS x (wherein x is a positive real number) is a titanium sulfide represented by.

[0442] V3S4, VS2, VS equation VS x (wherein x is a positive real number) is a vanadium sulfide represented by.

[0443] ·Fe3S4, FeS2, FeS equation x (wherein x is a positive real number) is an iron sulfide represented by.

[0444] ·Mo2S3, MoS2 equationMoS x (wherein x is a positive real number) is a molybdenum sulfide represented by.

[0445] SnS2, SnS equation SnS x (wherein x is a positive real number) is a tin sulfide represented by.

[0446] WS2 equation WS x (wherein x is a positive real number) is a tungsten sulfide represented by.

[0447] ·Sb2S3 equation SbS x (wherein x is a positive real number) is an antimony sulfide represented by.

[0448] ·Se5S3, SeS2, SeS equation SeS x (wherein x is a positive real number) is a selenium sulfide represented by.

[0449] Examples of nitrides that can be used as negative electrode active materials include Li3N, Li 3-x A x A lithium-containing nitride such as N (wherein A is either or both of Ni and Co, and 0<x<3).

[0450] These carbon materials, oxides, sulfides, and nitrides may be used alone or in combination of two or more. In addition, these carbon materials, oxides, sulfides, and nitrides may be crystalline or amorphous.

[0451] Examples of metals that can be used as the negative electrode active material include lithium metal, silicon metal, and tin metal.

[0452] Examples of alloys that can be used as negative electrode active materials include lithium alloys, silicon alloys, tin alloys, Cu2Sb, La3Ni2Sn7 and other alloys.

[0453] Examples of the lithium alloy include Li—Al, Li—Ni, Li—Si, Li—Sn, and Li—Sn—Ni.

[0454] Examples of the silicon alloy include Si—Zn.

[0455] Examples of the tin alloy include Sn—Mn, Sn—Co, Sn—Ni, Sn—Cu, and Sn—La.

[0456] These metals and alloys are mainly used alone as electrodes after being processed into foil forms, for example.

[0457] Among the above-mentioned negative electrode active materials, carbon materials with graphite such as natural graphite and artificial graphite as the main component are preferably used. This is because the potential of the negative electrode 120 hardly changes from the uncharged state to the fully charged state during charging (good potential flatness), the average discharge potential is low, and the capacity retention rate during repeated charge and discharge is high (good cycle characteristics).

[0458] The shape of the carbon material may be, for example, a flake shape such as natural graphite, a spherical shape such as mesocarbon microbeads, a fibrous shape such as graphitized carbon fibers, or an aggregate of fine powders.

[0459] Among the above negative electrode active materials, oxides are preferably used because of their high thermal stability and the difficulty in generating dendrites (dendrites) from Li metal. As the shape of the oxide, fibers or agglomerates of fine powders are preferably used.

[0460] (Negative electrode current collector)

[0461] The negative electrode current collector 122 of the negative electrode 120 may be a strip-shaped member formed of a metal material such as Cu, Ni, or stainless steel. Among them, a negative electrode current collector formed of Cu and processed into a thin film is preferred because it is difficult to form an alloy with lithium and is easy to process.

[0462] As methods for carrying the negative electrode active material layer 121 on the negative electrode collector 122, similarly to the case of the positive electrode 110, there can be listed: a method using pressure molding, a method of applying a paste of negative electrode mixture containing the negative electrode active material on the negative electrode collector 122, drying it, and then pressing and crimping it, and a method of applying a paste of negative electrode mixture containing the negative electrode active material on the negative electrode collector 122, drying it, and then sintering it.

[0463] (Solid electrolyte layer)

[0464] The solid electrolyte layer 130 includes the above-mentioned solid electrolyte (first solid electrolyte). When the positive electrode active material layer 111 includes a solid electrolyte, the solid electrolyte (first solid electrolyte) constituting the solid electrolyte layer 130 and the solid electrolyte (second solid electrolyte) contained in the positive electrode active material layer 111 may be the same substance. The solid electrolyte layer 130 functions as a medium for conducting lithium ions, and also functions as a separator for separating the positive electrode 110 from the negative electrode 120 to prevent short circuits.

[0465] The solid electrolyte layer 130 can be formed by depositing an inorganic solid electrolyte on the surface of the positive electrode active material layer 111 included in the positive electrode 110 by a sputtering method.

[0466] In addition, the solid electrolyte layer 130 can be formed by applying a paste mixture containing a solid electrolyte on the surface of the positive electrode active material layer 111 of the positive electrode 110 and drying it. The solid electrolyte layer 130 can also be formed by compression molding after drying and further pressurizing by cold isostatic pressing (CIP).

[0467] Furthermore, the solid electrolyte layer 130 can be formed by forming a solid electrolyte into pellets in advance, stacking the solid electrolyte pellets and the above-mentioned positive electrode active material sheet, and uniaxially pressing them in the stacking direction. The positive electrode active material sheet becomes the positive electrode active material layer 111 .

[0468] The positive electrode current collector 112 is further disposed on the positive electrode active material layer 111 of the obtained stack of the positive electrode active material layer 111 and the solid electrolyte layer 130. The solid electrolyte layer 130 and the positive electrode 110 can be formed by uniaxial pressing in the stacking direction and further sintering.

[0469] Such positive electrode 110 is in contact with solid electrolyte layer 130. Solid electrolyte layer 130 includes a first solid electrolyte.

[0470] The positive electrode 110 includes a positive electrode active material layer 111 in contact with a solid electrolyte layer 130 and a positive electrode current collector 112 stacked with the positive electrode active material layer 111. The positive electrode active material layer 111 includes a plurality of particles containing crystals of a lithium metal composite oxide (i.e., a positive electrode active material as one embodiment of the present invention) and a solid electrolyte (a second solid electrolyte) filled between the plurality of particles and in contact with the particles.

[0471] The solid electrolyte and particles contained in the positive electrode active material layer 111 are in contact with the solid electrolyte layer 130 . That is, the particles contained in the positive electrode active material layer 111 are in contact with the solid electrolyte contained in the positive electrode active material layer 111 and the solid electrolyte layer 130 .

[0472] It should be noted that it is not necessary for all particles (positive electrode active material) contained in the positive electrode active material layer 111 to be in contact with the solid electrolyte contained in the positive electrode active material layer 111 and the solid electrolyte layer 130 .

[0473] The positive electrode active material contained in the positive electrode active material layer 111 is in contact with the solid electrolyte contained in the positive electrode active material layer 111, thereby being electrically connected to the solid electrolyte contained in the positive electrode active material layer 111. In addition, the positive electrode active material contained in the positive electrode active material layer 111 is in contact with the solid electrolyte layer 130, thereby being electrically connected to the solid electrolyte layer 130. Furthermore, the solid electrolyte contained in the positive electrode active material layer 111 is in contact with the solid electrolyte layer 130, thereby being electrically connected to the solid electrolyte layer 130.

[0474] Through these, the positive electrode active material contained in the positive electrode active material layer 111 is directly or indirectly electrically connected to the solid electrolyte layer 130 .

[0475] The laminate 100 can be manufactured by laminating the negative electrode 120 with the solid electrolyte layer 130 provided on the positive electrode 110 as described above using a known method so that the negative electrode electrolyte layer 121 is in contact with the surface of the solid electrolyte layer 130. Thus, the solid electrolyte layer 130 and the negative electrode active material layer 121 are in contact and conduct.

[0476] As described above, for the obtained all-solid-state lithium-ion battery 100, the solid electrolyte layer 130 is provided in contact with the positive electrode 110 and the negative electrode 120 in a manner that does not short-circuit the positive electrode 110 and the negative electrode 120. The provided all-solid-state lithium-ion battery 100 is connected to an external power source and charged by applying a negative potential to the positive electrode 110 and a positive potential to the negative electrode 120.

[0477] Furthermore, the charged all-solid-state lithium-ion battery 100 is discharged by connecting a discharge circuit to the positive electrode 110 and the negative electrode 120 and energizing the discharge circuit.

[0478] According to the positive electrode active material for an all-solid-state lithium-ion battery having the above-described configuration, the initial discharge capacity can be increased.

[0479] According to the electrode having the above-described structure, since it contains the above-described positive electrode active material for an all-solid-state lithium ion battery, the initial discharge capacity of the all-solid-state lithium ion battery can be increased.

[0480] The all-solid-state lithium ion battery having the above-described configuration has the above-described positive electrode active material for an all-solid-state lithium ion battery and therefore exhibits an excellent initial discharge capacity.

[0481] The preferred embodiments of the present invention are described above with reference to the accompanying drawings, but the present invention is not limited to the examples. The shapes and combinations of the components shown in the above examples are examples, and various changes can be made based on design requirements within the scope of the present invention.

[0482] As an aspect, the present invention also includes the following scheme. It should be noted that the "positive electrode active material T" mentioned below refers to "a positive electrode active material, which is a positive electrode active material for an all-solid-state lithium-ion battery formed by particles containing crystals of a lithium metal composite oxide, wherein the particles have a hexagonal layered crystal structure belonging to the space group R-3m, and contain at least Li and a transition metal, and in a powder X-ray diffraction measurement using CuKα rays, the crystallite size L at the diffraction peak within the range of 2θ=18.7±1° 003 for The BET specific surface area of ​​the positive electrode active material is 0.2 m 2 / g or more and 2.0m 2 / g below".

[0483] (2-1) An application of using the positive electrode active material T in an all-solid-state lithium ion battery.

[0484] (2-2) An application of using the positive electrode active material T in a positive electrode used in an all-solid-state lithium ion battery.

[0485] (2-3) A use of the positive electrode active material T for manufacturing an all-solid-state lithium-ion battery.

[0486] (2-4) A use of the positive electrode active material T for producing a positive electrode used in an all-solid-state lithium-ion battery.

[0487] (2-A) The use according to (2-1), (2-2), (2-3), or (2-4), which is used for an all-solid-state lithium ion battery containing an oxide-based solid electrolyte as a solid electrolyte.

[0488] (3-1) The positive electrode active material T mentioned above is in contact with the solid electrolyte layer.

[0489] (3-1-1) The positive electrode active material T according to (3-1), wherein the solid electrolyte layer contains an oxide-based solid electrolyte.

[0490] (3-2) A positive electrode in contact with a solid electrolyte layer, the positive electrode comprising a positive electrode active material layer in contact with the solid electrolyte layer and a current collector on which the positive electrode active material layer is stacked, the positive electrode active material layer containing the positive electrode active material T.

[0491] (3-3) A positive electrode, which is a positive electrode in contact with a solid electrolyte layer, the positive electrode having a positive electrode active material layer in contact with the solid electrolyte layer and a collector stacked with the positive electrode active material layer, the positive electrode active material layer comprising the positive electrode active material T and a solid electrolyte, the positive electrode active material T comprising a plurality of particles, and the solid electrolyte being filled between the plurality of particles and in contact with the particles.

[0492] (3-4) The positive electrode according to (3-3), wherein the solid electrolyte and the particles contained in the positive electrode active material layer are in contact with each other in the solid electrolyte layer.

[0493] (3-A) The positive electrode according to (3-2), (3-3) or (3-4), wherein the solid electrolyte layer contains an oxide-based solid electrolyte.

[0494] (3-B) The positive electrode according to (3-2), (3-3), (3-4) or (3-A), wherein the solid electrolyte contained in the positive electrode active material layer is an oxide-based solid electrolyte.

[0495] (3-5) An all-solid-state lithium-ion battery comprising the positive electrode active material T described in any one of (3-1) and (3-1-1), or the positive electrode described in any one of (3-2), (3-3), (3-4), (3-A) and (3-B).

[0496] (4-1) A charging method for an all-solid-state lithium-ion battery, comprising: providing a solid electrolyte layer in contact with a positive electrode and a negative electrode in a manner that does not cause a short circuit between the positive electrode and the negative electrode; and applying a negative potential to the positive electrode and a positive potential to the negative electrode via an external power source, wherein the positive electrode contains the positive electrode active material T.

[0497] (4-2) A method for discharging a all-solid-state lithium-ion battery, which includes: providing by bringing a solid electrolyte layer into contact with a positive electrode and a negative electrode in a manner that does not cause short circuit between the positive electrode and the negative electrode; charging the all-solid-state lithium-ion battery by applying a negative potential to the positive electrode and a positive potential to the negative electrode through an external power source; and connecting a discharge circuit to the positive electrode and the negative electrode of the charged all-solid-state lithium-ion battery, wherein the positive electrode contains the positive electrode active material T.

[0498] (4-A) According to the charging method of the all-solid-state lithium-ion battery in (4-1), or the discharging method of the all-solid-state lithium-ion battery in (4-2), wherein the solid electrolyte layer contains an oxide-based solid electrolyte.

[0499] Examples

[0500] Hereinafter, the present invention will be described by way of examples, but the present invention is not limited to these examples.

[0501] <Composition analysis of positive electrode active material>

[0502] The composition analysis of the positive electrode active material manufactured by the method described below is carried out by the method described in the above <Composition analysis>. It should be noted that the composition of the lithium metal composite oxide is consistent with the composition corresponding to the above composition analysis result of the positive electrode active material and the composition formula (A). That is, the values of x, y, z, and w obtained by making the analysis result of the positive electrode active material correspond to the composition formula (A) can be regarded as the values of x, y, z, and w of the lithium metal composite oxide.

[0503] <Method for confirming particle shape>

[0504] The shape of the particles contained in the positive electrode active material is carried out by the method described in the above <Method for confirming particle shape>. In the case where the positive electrode active material contains single particles, its content rate is carried out by the above <Method for calculating the content rate of single particles>.

[0505] <Method for confirming crystal structure>

[0506] The crystal structure is carried out by the method described in the above <Method for confirming the crystal structure>.

[0507] <L 003 Measurement>

[0508] The above L 003 is obtained by the method described in the above <Method for measuring the above L 003 .

[0509] <Measurement of BET specific surface area>

[0510] The BET specific surface area is measured by the method described in the above <Method for Measuring BET Specific Surface Area>.

[0511] <Determination of the Atomic Weight of Impurities in the Positive Electrode Active Material>

[0512] The atomic weight of impurities contained in the positive electrode active material is measured by the method described in the above <Method for Measuring the Atomic Weight of Impurities in the Positive Electrode Active Material>.

[0513] <Determination of the Atomic Weight of Impurities in Potassium Sulfate Powder>

[0514] The atomic weight of impurities in potassium sulfate powder is measured by using potassium sulfate powder as an inert flux in the method described in the above <Method for Measuring the Atomic Weight of Impurities in Inert Flux>.

[0515] <L 003 / L 104 Calculation>

[0516] L 003 / L 104 The above <Ratio (L 003 / L 104 ) Calculation Method> is used for calculation.

[0517] <L 003 / L 110 Calculation>

[0518] L 003 / L 110 The above <Ratio (L 003 / L 110 ) Calculation Method> is used for calculation.

[0519] <Example 1>

[0520] (Manufacture of Positive Electrode Active Material 1)

[0521] After adding water into a reaction tank equipped with a stirrer and an overflow pipe, an aqueous sodium hydroxide solution is added, and the liquid temperature is maintained at 50 °C.

[0522] An aqueous nickel sulfate solution, an aqueous cobalt sulfate solution, and an aqueous manganese sulfate solution are mixed in a ratio such that the atomic ratio of Ni, Co, and Mn is 0.88:0.08:0.04 to prepare a mixed raw material solution 1.

[0523] Next, while stirring, the mixed raw material solution 1 and an aqueous ammonium sulfate solution as a complexing agent are continuously added into the reaction tank, and nitrogen gas is continuously introduced into the reaction tank. An aqueous sodium hydroxide solution is added dropwise as appropriate so that the pH of the solution in the reaction tank becomes 12.4 (when the liquid temperature of the aqueous solution is 40 °C) to obtain nickel-cobalt-manganese composite hydroxide particles.

[0524] The nickel-cobalt-manganese composite hydroxide particles were washed and then dehydrated using a centrifuge, separated, and dried at 120° C., thereby obtaining a nickel-cobalt-manganese composite hydroxide 1.

[0525] Nickel-cobalt-manganese composite hydroxide 1, lithium hydroxide powder and potassium sulfate powder 1 were weighed and mixed in a molar ratio of Li / (Ni+Co+Mn)=1.05, K2SO4 / (LiOH+K2SO4)=0.1, and then calcined at 800°C for 10 hours in an oxygen atmosphere to obtain a mixture 1 containing a lithium metal composite oxide.

[0526] The sum of the mass fractions of impurity atoms in the potassium sulfate powder 1 measured by the above-mentioned method was 0.008%.

[0527] Mixture 1 and pure water (water temperature 5° C.) were mixed in a ratio of 30 mass % of mixture 1 relative to the total amount of mixture 1 and pure water, and the obtained slurry was stirred for 10 minutes.

[0528] The slurry was dehydrated, and the obtained solid was washed with pure water (liquid temperature 5° C.) twice the mass of the mixture 1 used to adjust the slurry (rinsing step). The solid was dehydrated again, vacuum dried at 80° C. for 15 hours, and then vacuum dried at 150° C. for 8 hours, thereby obtaining a positive electrode active material 1.

[0529] (Evaluation of Positive Electrode Active Material 1)

[0530] The composition of the positive electrode active material 1 was analyzed and compared with the composition formula (A). The results showed that x=0.05, y=0.08, z=0.04, and w=0.

[0531] As a result of SEM observation of the positive electrode active material 1, it was found that the positive electrode active material 1 consisted of single particles, and the content of the single particles was 90% or more.

[0532] The crystal structure of the particles in the positive electrode active material 1 is a hexagonal layered crystal structure belonging to the space group R-3m. 003 for BET specific surface area is 1.58 m 2 / g, the atomic weight of impurities is 0.04%, L 003 / L 104 is 0.95, L 003 / L 110 It is 0.97.

[0533] <Example 2>

[0534] (Manufacturing of Positive Electrode Active Material 2)

[0535] A nickel sulfate aqueous solution, a cobalt sulfate aqueous solution and a manganese sulfate aqueous solution are mixed in a ratio of 0.91:0.07:0.02 of the atomic ratio of Ni, Co and Mn to prepare a mixed raw material solution 2; and a sodium hydroxide aqueous solution is added dropwise at appropriate times so that the pH of the solution in the reaction tank becomes 12.3 (when the liquid temperature of the aqueous solution is 40°C). Except for this, the same operation as in Example 1 is performed to obtain a nickel-cobalt-manganese composite hydroxide 2.

[0536] Nickel-cobalt-manganese composite hydroxide 2, lithium hydroxide powder and potassium sulfate powder 1 are weighed and mixed in a molar ratio of Li / (Ni+Co+Mn)=1.26, K2SO4 / (LiOH+K2SO4)=0.1, and then calcined at 790°C for 10 hours in an oxygen atmosphere to obtain a mixture 2 containing a lithium metal composite oxide.

[0537] Mixture 2 and pure water (water temperature 5° C.) were mixed in a ratio of 30% by mass of mixture 2 relative to the total amount of mixture 2 and pure water, and the obtained slurry was stirred for 10 minutes.

[0538] The slurry was dehydrated, and the obtained solid was washed with pure water (water temperature 5°C) twice the mass of the mixture 2 used to prepare the slurry (rinsing step). The solid was dehydrated again, vacuum dried at 80°C for 15 hours, and then vacuum dried at 150°C for 8 hours.

[0539] The obtained powder was screened using a cyclone screen (manufactured by FREUND-TURBO CO., LTD.) to obtain a positive electrode active material 2. The operating conditions and screening conditions of the cyclone screen were set as follows.

[0540] [Operation conditions and screening conditions of cyclone screen]

[0541] The obtained lithium metal composite oxide was sieved with a cyclone sieve (TS125×200 model, manufactured by FREUND-TURBO Co., Ltd.) The operating conditions of the cyclone sieve were set as follows.

[0542] (Cyclone screen operating conditions)

[0543] Screen used: 45μm mesh, blade speed: 1800rpm, supply speed: 50kg / hour

[0544] (Evaluation of Positive Electrode Active Material 2)

[0545] The composition of the positive electrode active material 2 was analyzed and compared with the composition formula (A). The results showed that x=0.02, y=0.07, z=0.02, and w=0.

[0546] As a result of SEM observation of the positive electrode active material 2, it was found that the positive electrode active material 2 consisted of single particles, and the content of the single particles was 90% or more.

[0547] The crystal structure of the particles in the positive electrode active material 2 is a hexagonal layered crystal structure belonging to the space group R-3m. 003 for BET specific surface area is 1.18 m 2 / g, the atomic weight of impurities is 0.04%, L 003 / L 104 is 1.20, L 003 / L 110 is 1.27.

[0548] <Example 3>

[0549] (Manufacturing of Positive Electrode Active Material 3)

[0550] A precipitate containing nickel-cobalt-manganese composite hydroxide was obtained in the same manner as in Example 1 except that a sodium hydroxide aqueous solution was added dropwise at an appropriate time so that the pH of the solution in the reaction tank became 11.2 (when the liquid temperature of the aqueous solution was 40°C) and the liquid temperature was maintained at 70°C.

[0551] The obtained precipitate was pulverized using a reverse jet mill (100AFG model, manufactured by Hosokawa Micron Co., Ltd.) to obtain a nickel-cobalt-manganese composite hydroxide 3. The operating conditions of the reverse jet mill were set as follows.

[0552] (Operation conditions of reverse jet mill)

[0553] Crushing pressure: 0.59MPa, classification speed: 17000rpm, supply speed: 2kg / hour

[0554] The positive electrode active material 3 was obtained in the same manner as in Example 1 except that the nickel-cobalt-manganese composite hydroxide 3, lithium hydroxide powder and potassium sulfate powder 1 were weighed and mixed in a molar ratio of Li / (Ni+Co+Mn)=1.20 and K2SO4 / (LiOH+K2SO4)=0.1.

[0555] (Evaluation of Positive Electrode Active Material 3)

[0556] The composition of the positive electrode active material 3 was analyzed and compared with the composition formula (A). The results showed that x=0.20, y=0.08, z=0.04, and w=0.

[0557] As a result of SEM observation of the positive electrode active material 3, it was found that the positive electrode active material 3 consisted of single particles, and the content of the single particles was 90% or more.

[0558] The crystal structure of the particles in the positive electrode active material 3 is a hexagonal layered crystal structure belonging to the space group R-3m. 003 for BET specific surface area is 1.86 m 2 / g, the atomic weight of impurities is 0.03%, L 003 / L 104 is 1.03, L 003 / L 110 is 1.11.

[0559] <Comparative Example 1>

[0560] (Manufacturing of Positive Electrode Active Material 4)

[0561] After water was added to a reaction tank equipped with a stirrer and an overflow pipe, an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 50°C.

[0562] A nickel sulfate aqueous solution, a cobalt sulfate aqueous solution, and a manganese sulfate aqueous solution were mixed at an atomic ratio of Ni, Co, and Mn of 0.55:0.20:0.25 to prepare a mixed raw material solution 4.

[0563] Next, the mixed raw material solution 4 and an aqueous solution of ammonium sulfate as a complexing agent were continuously added to the reaction tank under stirring, and nitrogen was continuously introduced into the reaction tank. Sodium hydroxide aqueous solution was added dropwise at appropriate times so that the pH of the solution in the reaction tank reached 12.0 (when the temperature of the aqueous solution was 40° C.), thereby obtaining nickel-cobalt-manganese composite hydroxide particles.

[0564] The obtained nickel-cobalt-manganese composite hydroxide particles were washed and then dehydrated using a centrifuge, and then separated and dried at 120° C., thereby obtaining a nickel-cobalt-manganese composite hydroxide 4.

[0565] The nickel-cobalt-manganese composite hydroxide particles 4 and lithium hydroxide powder were weighed and mixed at a molar ratio of Li / (Ni+Co+Mn)=1.02.

[0566] Thereafter, the resultant was fired at 650° C. for 5 hours in an oxygen atmosphere.

[0567] Furthermore, the resultant was fired at 970° C. for 4 hours in an air atmosphere.

[0568] Furthermore, the resultant was fired at 760° C. for 5 hours in an air atmosphere.

[0569] The obtained powder was sieved using an ultrasonic generator (manufactured by Artech Ultrasonic Systems (model: PNS35-50-S)) to obtain positive electrode active material 4. Sieving was performed by vibrating a stainless steel sieve having a mesh size of 45 μm and a diameter of 200 mm at an ultrasonic output of 50 W.

[0570] (Evaluation of Positive Electrode Active Material 4)

[0571] The composition of the positive electrode active material 4 was analyzed and compared with the composition formula (A). The results showed that x=0.05, y=0.20, z=0.25, and w=0.

[0572] As a result of SEM observation of the positive electrode active material 4, it was found that the positive electrode active material 4 contained primary particles and secondary particles, and the content of single particles was 0%.

[0573] The crystal structure of the particles in the positive electrode active material 4 is a hexagonal layered crystal structure belonging to the space group R-3m. 003 for BET specific surface area is 0.63 m 2 / g, the atomic weight of impurities is 0.04%, L 003 / L 104 is 0.94, L 003 / L 110 is 1.02.

[0574] <Comparative Example 2>

[0575] (Manufacturing of Positive Electrode Active Material 5)

[0576] After water was added to a reaction tank equipped with a stirrer and an overflow pipe, an aqueous sodium hydroxide solution was added and the liquid temperature was maintained at 50°C.

[0577] A nickel sulfate aqueous solution, a cobalt sulfate aqueous solution, and a manganese sulfate aqueous solution were mixed at an atomic ratio of Ni, Co, and Mn of 0.55:0.20:0.25 to prepare a mixed raw material solution 5 .

[0578] Next, the mixed raw material solution 5 and an aqueous ammonium sulfate solution as a complexing agent were continuously added to the reaction tank under stirring. A sodium hydroxide solution was added dropwise at an appropriate time so that the pH of the solution in the reaction tank reached 12.0 (when the temperature of the aqueous solution was 40° C.), thereby obtaining nickel-cobalt-manganese composite hydroxide particles.

[0579] The obtained nickel-cobalt-manganese composite hydroxide particles were washed, isolated, and dried at 120° C., thereby obtaining nickel-cobalt-manganese composite hydroxide 5 .

[0580] The nickel-cobalt-manganese composite hydroxide particles 5 and the lithium hydroxide monohydrate powder were weighed and mixed at a molar ratio of Li / (Ni+Co+Mn)=1.05.

[0581] Thereafter, the resulting product was fired at 650° C. for 5 hours in an oxygen atmosphere.

[0582] Then, the resulting product was fired at 960° C. for 5 hours in an oxygen atmosphere.

[0583] Then, the resulting film was fired at 1015° C. for 5 hours in an oxygen atmosphere.

[0584] The mixture was further calcined at 400° C. for 5 hours in an air atmosphere to obtain a lithium metal composite oxide.

[0585] The obtained lithium metal composite oxide was pulverized by a pin mill pulverizer (Impact Mill AVIS100, manufactured by Mill Systems Co., Ltd.) to obtain a positive electrode active material 5. The operating conditions of the pin mill pulverizer were set as follows.

[0586] (Operation conditions of pin mill)

[0587] Rotation speed: 16000rpm, supply speed: 8kg / hour

[0588] (Evaluation of Positive Electrode Active Material 5)

[0589] The composition of the positive electrode active material 5 was analyzed and compared with the composition formula (A). The results showed that x=0.03, y=0.20, z=0.25, and w=0.

[0590] As a result of SEM observation of the positive electrode active material 5 , it was found that the positive electrode active material 5 consisted of single particles, and the content of the single particles was 90% or more.

[0591] The crystal structure of the particles in the positive electrode active material 5 is a hexagonal layered crystal structure belonging to the space group R-3m. 003 for BET specific surface area is 0.41 m 2 / g, the atomic weight of impurities is 0.06%, L 003 / L 104 is 0.99, L 003 / L 110 is 1.02.

[0592] <Comparative Example 3>

[0593] (Positive electrode active material 6)

[0594] A commercial product of LiCoO2 was evaluated as positive electrode active material E1. As positive electrode active material 6, a commercial product of LiCoO2 manufactured by Nippon Chemical Industry Co., Ltd. (CellSeed C-5H) was used.

[0595] (Evaluation of Positive Electrode Active Material 6)

[0596] As a result of SEM observation of the positive electrode active material 6 , it was found that the positive electrode active material 6 consisted of a single particle, and the content of the single particle was 100%.

[0597] The crystal structure of the particles in the positive electrode active material 6 is a hexagonal layered crystal structure belonging to the space group R-3m. 003 for BET specific surface area is 0.44 m 2 / g, the atomic weight of impurities is 0.02%, L 003 / L 104 is 0.65, L 003 / L 110 It is 0.62.

[0598] <Manufacturing of all-solid-state lithium-ion batteries>

[0599] (Manufacturing of positive electrode active material sheet)

[0600] An all-solid-state lithium ion battery is produced by the method described in the above-mentioned <Production of an all-solid-state lithium ion secondary battery> using the positive electrode active material obtained by the above-mentioned production method.

[0601] <Determination of initial discharge capacity>

[0602] Using the fabricated all-solid-state lithium ion battery, the initial discharge capacity was calculated by the method described in the above <Measurement of Initial Discharge Capacity>.

[0603] <Manufacturing of Liquid Lithium Secondary Batteries>

[0604] (Manufacturing of positive electrode for lithium secondary battery)

[0605] The positive electrode active material obtained by the above-mentioned manufacturing method, the conductive material (acetylene black) and the binder (PVdF) were added and kneaded in a ratio of positive electrode active material: conductive material: binder = 92:5:3 (mass ratio) to prepare a paste positive electrode mixture. NMP was used as an organic solvent when preparing the positive electrode mixture.

[0606] The obtained positive electrode mixture was applied to a 40 μm thick Al foil serving as a current collector and vacuum dried at 150° C. for 8 hours to obtain a positive electrode for a lithium secondary battery. The electrode area of ​​the positive electrode for a lithium secondary battery was set to 1.65 cm 2 .

[0607] (Manufacturing of lithium secondary battery (coin-type half-cell))

[0608] The following operations were performed in a glove box under an argon atmosphere.

[0609] The positive electrode for lithium secondary battery produced in (Production of positive electrode for lithium secondary battery) was placed on the lower cover of a component for coin-type battery R2032 (produced by Hohsen Co., Ltd.) with the aluminum foil facing downward, and a separator (polyethylene porous film) was placed thereon.

[0610] 300 μl of an electrolyte solution was injected therein. As the electrolyte solution, a solution obtained by dissolving LiPF6 in a mixed solution of ethylene carbonate, dimethyl carbonate and ethylmethyl carbonate at a ratio of 30:35:35 (volume ratio) at a ratio of 1.0 mol / l was used.

[0611] Next, metallic lithium was used as the negative electrode, the negative electrode was placed on the upper side of the laminated film separator, a top cover was put on via a gasket, and riveted with a riveting machine to produce a lithium secondary battery (coin-type half-cell R2032, sometimes referred to as a "half-cell" hereinafter).

[0612] <Determination of initial discharge capacity>

[0613] Using the prepared half-cell, the first charge and discharge test was carried out under the following conditions.

[0614] <First charge and discharge test conditions>

[0615] Test temperature: 25℃

[0616] Maximum charging voltage 4.3V, charging time 6 hours, charging current 0.2CA, cut-off current 0.05CA, constant current and constant voltage charging

[0617] Minimum discharge voltage 2.5V, discharge time 5 hours, discharge current 0.2CA, constant current discharge

[0618] The crystal structures of the positive electrode active materials of Examples 1 to 3 and Comparative Examples 1 to 3, L 003 , BET specific surface area, impurity atomic weight, L 003 / L 104 and L 003 / L 110 It is recorded in Table 1.

[0619] [Table 1]

[0620]

[0621] Table 2 shows the initial discharge capacities of the liquid lithium secondary batteries and all-solid lithium ion batteries using the positive electrode active materials of Examples 1 to 3 and Comparative Examples 1 to 3.

[0622] [Table 2]

[0623]

[0624] As a result of the evaluation, all solid-state lithium ion batteries using the positive electrode active materials of Examples 1 to 3 all showed high first discharge capacities. In contrast, the positive electrode active materials of Comparative Examples 1 to 3 showed low first discharge capacities.

[0625] Liquid lithium ion secondary batteries were produced and evaluated for the positive electrode active materials of Examples and Comparative Examples. The results are shown in Table 2, indicating that all the positive electrode active materials were evaluated to be suitably usable.

[0626] It is thus known that even positive electrode active materials that work well in liquid lithium ion secondary batteries have large differences in initial discharge capacity when made into all-solid lithium ion secondary batteries. The positive electrode active material for the all-solid lithium ion secondary battery of the present invention shows a good initial discharge capacity.

[0627] As can be seen from the above, the present invention is useful.

[0628] Explanation of symbols

[0629] 100: laminate, 110: positive electrode, 111: positive electrode active material layer, 112: positive electrode current collector, 113: external terminal, 120: negative electrode, 121: negative electrode electrolyte layer, 122: negative electrode current collector, 123: external terminal, 130: solid electrolyte layer, 200: outer package, 200a: opening, 1000: all-solid-state lithium-ion battery

Claims

1. A positive electrode active material for an all-solid-state lithium-ion battery, which is a positive electrode active material for an all-solid-state lithium-ion battery formed of particles containing crystals of a lithium metal composite oxide, The particles have a hexagonal layered crystal structure belonging to the space group R-3m, contain at least Li and a transition metal, and have a crystallite size L at a diffraction peak within the range of 2θ=18.7±1° in a powder X-ray diffraction measurement using CuKα radiation. 003 for the following, The BET specific surface area of ​​the positive electrode active material for the all-solid-state lithium-ion battery is 0.2 m 2 / g or more and 2.0m 2 / g or less, In the powder X-ray diffraction measurement, the L 003 The crystallite size L at the diffraction peak in the range of 2θ = 64.5 ± 1° 110 The ratio of L 003 / L 110 is 0.65 or more and 3.00 or less, In the powder X-ray diffraction measurement, the L 003 The crystallite size L at the diffraction peak in the range of 2θ = 44.6 ± 1° 104 The ratio of L 003 / L 104 is 0.70 or more and 3.00 or less, The positive electrode active material for the all-solid-state lithium-ion battery is in contact with the solid electrolyte layer. 2 . The positive electrode active material for an all-solid-state lithium ion battery according to claim 1 , which is used in an all-solid-state lithium ion battery containing an oxide-based solid electrolyte.

3. The positive electrode active material for an all-solid-state lithium ion battery according to claim 1 or 2, wherein: The sum of the mass fractions of K atoms, Fe atoms, Cr atoms, Cu atoms, Ca atoms, Mg atoms and Na atoms relative to the total mass of the positive electrode active material for an all-solid-state lithium ion battery is 0.03% to 1.0%.

4. The positive electrode active material for an all-solid-state lithium ion battery according to claim 1 or 2, wherein In the powder X-ray diffraction measurement, the L 003 The crystallite size L at the diffraction peak in the range of 2θ = 44.6 ± 1° 104 The ratio of L 003 / L 104 It is 0.90 or more and 2.00 or less.

5. The positive electrode active material for an all-solid-state lithium-ion battery according to claim 1 or 2, wherein: In the powder X-ray diffraction measurement, the L 003 The crystallite size L at the diffraction peak in the range of 2θ = 64.5 ± 1° 110 The ratio of L 003 / L 110 It is 0.80 or more and 2.00 or less.

6. The positive electrode active material for an all-solid-state lithium ion battery according to claim 1 or 2, wherein: The transition metal is at least one element selected from the group consisting of Ni, Co, Mn, Ti, V, and W.

7. The positive electrode active material for an all-solid-state lithium-ion battery according to claim 6, wherein The lithium metal composite oxide is represented by the following composition formula (A): Li[Li x (Ni (1-y-z-w) Co y Mn z M w ) 1-x ]O2 composition formula (A) Here, M is one or more elements selected from the group consisting of Ti, Al, W, B, Mo, Nb, Zn, Sn, Zr, Ga and V, and satisfies -0.10≤x≤0.30, 0≤y≤0.40, 0≤z≤0.40 and 0≤w≤0.

10.

8. The positive electrode active material for an all-solid-state lithium-ion battery according to claim 7, wherein In the composition formula (A), y>0 and z+w>0 are satisfied.

9. The positive electrode active material for an all-solid-state lithium-ion battery according to claim 7, wherein In the composition formula (A), 1-yzw≥0.50 and y≤0.30 are satisfied.

10. The positive electrode active material for an all-solid-state lithium ion battery according to claim 1 or 2, wherein: The particles are composed of primary particles, secondary particles that are aggregates of the primary particles, and single particles that exist independently of the primary particles and the secondary particles. The content of the single particles in the particles is 20% or more. 11 . An electrode comprising the positive electrode active material for an all-solid-state lithium ion battery according to claim 1 .

12. The electrode according to claim 11, further comprising a solid electrolyte.

13. An all-solid-state lithium-ion battery comprising a positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, The solid electrolyte layer comprises a first solid electrolyte, The positive electrode includes a positive electrode active material layer in contact with the solid electrolyte layer and a current collector on which the positive electrode active material layer is stacked. The positive electrode active material layer includes the positive electrode active material for an all-solid-state lithium ion battery according to any one of claims 1 to 10.

14. The all-solid-state lithium-ion battery according to claim 13, wherein: The positive electrode active material layer includes the positive electrode active material for an all-solid-state lithium-ion battery and a second solid electrolyte.

15. The all-solid-state lithium-ion battery according to claim 14, wherein: The first solid electrolyte and the second solid electrolyte are made of the same material.

16. The all-solid-state lithium-ion battery according to any one of claims 13 to 15, wherein The first solid electrolyte has an amorphous structure.

17. The all-solid-state lithium-ion battery according to any one of claims 13 to 15, wherein The first solid electrolyte is an oxide-based solid electrolyte.

18. Use of the positive electrode active material in an all-solid-state lithium-ion battery or a positive electrode used in an all-solid-state lithium-ion battery, The positive electrode active material is a positive electrode active material for an all-solid-state lithium-ion battery formed of particles containing crystals of a lithium metal composite oxide. The particles have a hexagonal layered crystal structure belonging to the space group R-3m, contain at least Li and a transition metal, and have a crystallite size L at a diffraction peak within the range of 2θ=18.7±1° in a powder X-ray diffraction measurement using CuKα radiation. 003 for the following, The BET specific surface area of ​​the positive electrode active material for the all-solid-state lithium-ion battery is 0.2 m 2 / g or more and 2.0m 2 / g or less, In the powder X-ray diffraction measurement, the L 003 The crystallite size L at the diffraction peak in the range of 2θ = 64.5 ± 1° 110 The ratio of L 003 / L 110 is 0.65 or more and 3.00 or less, In the powder X-ray diffraction measurement, the L 003 The crystallite size L at the diffraction peak in the range of 2θ = 44.6 ± 1° 104 The ratio of L 003 / L 104 It is 0.70 or more and 3.00 or less.

Citation Information

Patent Citations

  • High density nickel hydroxide coprecipitated with cobalt and manganese, and method for producing the same

    JP2002201028A

  • Solid electrolyte composition, solid electrolyte-containing sheet, all-solid type secondary battery, and methods for manufacturing solid electrolyte-containing sheet and all-solid type secondary battery

    JP2018014317A

  • Cartridge adapter, cartridge unit, and method for assembling cartridge

    JP2020006339A

  • Positive electrode active material for all-solid-state lithium-ion battery, electrode and all-solid-state lithium-ion battery

    JP6734491B1

  • Positive electrode active material for lithium secondary batteries, positive electrode for lithium secondary batteries, and lithium secondary battery

    CN107112528A